Investigating the mechanisms of liver injury in zebrafish induced by polystyrene microplastics and 17α-methyltestosterone based on the gut-liver axis - Weiya Rong; Zijun Xiong; Chang Hu; Haiyan Zhao; Lu Cao; Jiaoxin Xie; Weiwei Wang; Jing Song; Xianzong Wang; Yu Liu; Shaozhen Liu (Environmental Pollution, 2026)

Influence of the intrinsic properties of nanopipettes on sensing performance - Wenhao Ma; Rong Tian; Shixuan He; Shaoxi Fang; Bohua Yin; Yongjia Wang; Ting Weng; Wanyi Xie; Danqun Huo; Changjun Hou; Deqiang Wang (Chemical Engineering Journal, 2026)

Spatiotemporal dynamics of PFAS ecological risk in major Chinese river networks: a data-driven assessment (2011–2024) - Letian Zhang; Wei Lin; Zhouyun Xie; Yewei Wang; Rong Wu; Jiaqi Yang; Nanyang Yu; Xiaodong Li; Jie Liang (Water Research, 2026)

Supply-limited weathering across global water-limited mountains governed by water availability and denudation - Haopeng Geng; Songbo Dai; Jian Zhang; Rong Xie (Geomorphology, 2026)

Ophiopogon japonicus fibrous root polysaccharides as stabilizers for zein-curcumin nanoparticles: Extraction-regulated structural conformations, antioxidant activities, and delivery performance - Jiaqi Chen; Xiao Yang; Wen Zhang; Yunlu Wei; Yisheng Jibu; Min Xia; Xiangyu Zeng; Shufan Xie; Rong Wang (Food Bioscience, 2026)

Integrated metabolomics and network pharmacology reveal metabolic remodeling and potential antioxidant mechanisms in fermented Lycium barbarum - Jianyu Huang; Dengmi Wang; Ziyi Yang; Jinrou Xie; Die die Wang; Rong Guo; Dunhua Liu; Song Miao; Jicheng Chen (Food Bioscience, 2026)

Efficient capture of radioactive iodine by a two-dimensional metal-organic framework - Jiaxing Deng; Xingwei Xie; Pengjun Duan; Xiang Ni; Chaoxiang Liu; Hanya Zheng; Rong Cheng; Xiang Zheng; Jianzhong Zheng (Chemical Engineering Journal, 2026)

Iodine vapor adsorption induced liquid conductive metal-organic frameworks for self-powered humidity sensing - Weifang Zhang; Yuan Cheng; Lingling Zhuang; Ruijin Jiang; Cui-Cui Ji; Rong-Rong Xie; Yupeng Chen (Chemical Engineering Journal, 2026)

Modulation mechanism of Mesona chinensis polysaccharide on structural evolution of corn starch cryogel during gelatinization - Liyuan Rong; Jieyan Li; Jieqiong Lin; Jia Kong; Mingyue Shen; Jianhua Xie (Carbohydrate Polymers, 2026)

Molecular mechanism of anammox granular sludge disintegration caused by polyethylene terephthalate micro/nanoplastics: a new perspective based on quorum sensing - Chaofan Xie; Dongyue Li; Jun Li; Jiarui Li; Muchen Yin; Yanshuo Wu; Chi Zhang; Rong Luo; Yuxi Zhu; Zehao Zhang; Zhaoming Zheng; Yongzhen Peng (Bioresource Technology, 2026)

Persistent contamination, limited accumulation: In-situ isotope tracing reveals fast thallium turnover in natural waters - Chenghong Yu; Hongkai Wang; Wenze Xiao; Qiao-Guo Tan; Rong Chen; Lihua Liu; Nengwang Chen; Minwei Xie (Aquatic Toxicology, 2026)

Cascade-amplified oxidative stress coupled with tryptophan metabolic blockade for synergistic cancer immunotherapy - Xiaoya Wu; Yu Guo; Jianxin Rong; Jiahui Cong; Chunyong Liang; Zhigang Xie; Xiuli Hu (Chemical Engineering Journal, 2026)

Nanoconfinement-enhanced peroxymonosulfate activation by Co single atoms in hollow mesoporous carbon: Roles of active-site chemistry and mesoscale confinement - Hao Luo; Junli Zheng; Jiaxin Liu; Junjun Ma; Rui He; Chuqi Huang; Rong Xie; Qintie Lin (Water Research, 2026)

Regulatory role of the keystone taxa Dokdonella in bacterial network stability under grazing disturbance in alpine meadows - Hainian Lu; Jiaoyang Du; Yongli Xie; Yu Zou; Xiujin Zhang; Dingan Gao; Xiaohui Wu; Chaokun Wang; Rong Wang (Rhizosphere, 2026)

Fipronil and its metabolites in a tropical estuary: multi-compartment distribution, trophic transfer, and risk assessment - Yu-Han Xie; Can Huo; Zhi-Yan Wang; Shan-Shan Yao; Heng-Xiang Li; Yu Zhong; Xiao-Ping Huang; Xiang-Rong Xu (Marine Environmental Research, 2026)

Toxicity-weighted source prioritization of PFAS and antibiotics in an urban watershed - Letian Zhang; Jiaqi Yang; Nanyang Yu; Hao Luo; Zhouyun Xie; Yewei Wang; Rong Wu; Wei Lin; Xiaodong Li; Jie Liang (Journal of Hazardous Materials, 2026)

Heat stress modulates the size-dependent effects of aminated polystyrene particles on a marine diatom - Ting-Ting Xu; Zhen-Liang Li; Zhi-Yan Wang; Yu-Han Xie; Heng-Xiang Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2026)

An inflammation-targeted hydrogel for the synergistic treatment of colorectal cancer and associated neuropsychiatric dysfunction - Keying Chen; Na Li; Anni Ren; Lingling Yang; Pei Xie; Yong Gao; Yanwu Li; Ying Tang; Rong Zhang; Huafeng Pan; Bangjiang Fang; Tongkai Chen; et al. (Chemical Engineering Journal, 2026)

Moderate grazing disturbance enhances network stability and ecological functions of rhizobacteria in Alpine meadows: Identification and validation of Core genera - Hainian Lu; Jiaoyang Du; Yongli Xie; Dingan Gao; Xiaohui Wu; Feifei Chang; Liyang Duan; Xuerui Wang; Rong Wang (CATENA, 2026)

Investigation of the regulatory effects of the initial oxidation–reduction potential on lactic acid-producing bacteria in culture and silage fermentation and its metabolic mechanism - Mengxin Li; Yuanjiang Rong; Qiang Yu; Ya Su; Yulong Xi; Yixi Long; Yixiao Xie; Hong Sun; Jun Hao; Fuyu Yang; Yulong Zheng (Bioresource Technology, 2026)

The meteorological and anthropogenic drivers of O3 and PM2.5 pollution in China's Ningbo based on WRF-CMAQ-ISAM - YuZhan Xie; Tijian Wang; Pulong Chen; Kuanguang Zhu; Tao Niu; Rong Li; Mengmeng Li; Hao Wu; Yawei Qu; Xu Liu; Congwu Huang (Atmospheric Pollution Research, 2026)

Daily water level forecasting with limited data using cluster- and season-based transfer learning - Zexi Huang; Wei Sun; Yutong Xie; Xinlin Chen; Zerong Rong; Yingying Hong (Science of The Total Environment, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Industrial waste salt pyrolysis toward zero liquid discharge: Enabling efficient organic removal and resource recovery - Zhi-Bo Li; Xiang-Lin Chang; Juan Xie; Rong Chen; Xiaochang C. Wang; Bao-Shan Xing (Journal of Water Process Engineering, 2026)

Crop spatial concentration enhances water productivity while threatening regional agricultural water sustainability - Hongrong Huang; Qiangqiang Rong; Yiping Wu; Yulei Xie; Wei Wang; Xiangxiang Ji; Zenghui Xu; Jie Gao; Meirong Su; La Zhuo (Journal of Hydrology, 2026)

Corrigendum to “State-selective engineering in luminescent metal-organic frameworks: Ligand-to-ligand charge transfer activates superior photocatalytic sterilization in Wei River” [J Hazard Mater 500 (2025) 140448] - Liang Qiu; Yajie Zhang; Baiyu Wu; Wenqiong Liu; Yiwen Xie; Jing He; Kerang Huang; Jianlong Wang; Rong Wang (Journal of Hazardous Materials, 2026)

N(7)-methylguanosine modification of mitochondrial tRNA-Trp drives myocardial injury induced by silicon carbide nanoparticles - Qingping Liu; Tao Zhang; Mengruo Wang; Peilin Zheng; Wen Gu; Yujia Xie; Yaxian Pang; Lei Bao; Haijing Zhang; Yujie Niu; Yufei Dai; Rong Zhang (Journal of Hazardous Materials, 2026)

Hypoallergenic casein peptides derived from strain–enzyme combined hydrolysis attenuate allergic immune responses and modulate gut microbiota in mice - Xiaomei Zhang; Minting Rong; Jinlan Xie; Ting Wang; Zhigui He; Aiying Xu; Xiaomeng Wu; Haizhu Wu (International Dairy Journal, 2026)

Cold acclimation reprograms the flavor metabolome of fresh tea leaves to enhance sensory quality: Insights from metabolomics, GC-O, and transcriptomics - Chenyu Shao; Rong Xu; Yuqi Luo; Mingyue Zhao; Ting Wu; Lihua Zhu; Siyi Xie; Qifang Jin; Lan Chen; Songyan Huang; Juan Mao; Jianan Huang; et al. (Food Research International, 2026)

An innovative immobilization-free homogeneous electrochemical strategy facilitated by buoyancy -magnetism separation for evaluating the acetamiprid in food - Ya-Rong Xie; Yue-Han Wang; Jia-Le Wang; Li-Ping Jia; Wei Zhang; Lei Shang; Xiao-Jian Li; Qing-Wang Xue; Huai-Sheng Wang; Rong-Na Ma (Food Chemistry, 2026)

SRP-LNP@IL-10 nanotherapy combined with neural stem cells couples inflammation suppression with neural regeneration after spinal cord injury via the STAT3-SOCS3-BDNF axis - Ying Zhang; Honghai You; Yongxiang Zhang; Haoteng Chen; Yifeng Zheng; Weiwei Sun; Rong Xie; Tong Zhao (Chemical Engineering Journal, 2026)

Pentoxifylline targets TLR4/MyD88/NF-κB signaling to ameliorate neuroinflammation and metabolic dysfunction in a rat model of chronic hypoperfusion-induced vascular cognitive impairment - Xiaohan Wang; Bingchuan Xie; Xiaoyang Yuan; Jiaying Rong; Xiaojing Lv; Qingying Ma; Li Shen; Bing Han (Metabolic Brain Disease, 2026)

Unraveling the complex interplay between glymphatic function, age, and brain structure in school-aged children with autism spectrum disorder - Zhongfeng Xie; Di Zhou; Shuchao Wang; Ting Hua; Hong Chen; Rong Yang; Yujiao Gong; Guangyu Tang; Lin Zhang; Xiaowen Xu (Brain Imaging and Behavior, 2026)

The phytosulfokine receptor ClPSKR1 negatively regulates watermelon resistance to Fusarium wilt - Chunmei Xie; Rong Tang; Man Zhang (Physiological and Molecular Plant Pathology, 2026)

Paphia undulata enhances sedimentary CH4 and N2O emissions via divergent microbial mechanisms - Ziyun Zhong; Yuxin Ruan; Jing Qian; Minwei Xie; Qiaoguo Tan; Rong Chen (Marine Environmental Research, 2026)

Protein amyloid-like fibrils derived from cereals: Formation, structural characteristics, and applications - Boruo Yang; Haoju Zhao; Zihang Fu; Liting Shen; Liyuan Rong; Jianhua Xie (Food Research International, 2026)

Dual-function photosensitive bacterial cellulose film for real-time meat freshness monitoring and rapid sterilization - Rui Chen; Yiwen Xie; Yunyan Bai; Kerang Huang; Xuemei Liao; Yulin Liu; Rong Wang (Food Control, 2026)

Ion-gas synergistically reshape microenvironment for bone immune regulation and osteogenic regeneration - Kun Wang; Zhenhua Wang; Bing Xiao; Chang Cai; Jiaqiang Zhang; Yifan Zhang; Liuzhi Wu; Yelin Wu; Ke Rong; Xiaoxing Xie; Guohua Xu (Chemical Engineering Journal, 2026)

Enzymatically synthesized native-like guaiacyl dehydrogenation polymer as a formaldehyde-free adhesive for high-strength, water-resistant plywood - Rui Luo; Wenhao Liu; Qian Tu; Yuanpu Wang; Junjun Chen; Junxian Xie; Rong Zhang; Nianjie Feng; Peng Wang (Chemical Engineering Journal, 2026)

Position-sequence enhanced meta-reinforcement learning with adaptive fine-tuning for few-shot GNSS positioning correction - Zhenni Li; Hui Li; Jianhao Tang; Rong Yuan; Xuesong Tan; Maodeng Li; Shengli Xie (GPS Solutions, 2026)

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

Isolation, identification, and disease-protective potential of Pseudomonas monsensis DBFF02 against Saprolegnia infection in grass carp - Guofan Zhang; Kunyan Li; Yuyuan Peng; Simei He; Chen Li; Rong Fan; Jiajie Xie; Linger Qian; Xinran Long; Jiayi Wang; Jiatao Yang; Yanmin He; et al. (Aquaculture, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Association of phthalate exposure during early pregnancy with fetal growth and the effect modification by gestational stress - Nian Wu; Zhongmei Hu; Xinyi Xiao; Shimin Xiong; Xingyan Liu; Yan Xie; Rong Zeng; Kunming Tian; Xubo Shen; Yuanzhong Zhou; Yijun Liu (International Journal of Hygiene and Environmental Health, 2026)

Proanthocyanidin/laccase-mediated cross-linking enhances the structural stability and rheological properties of collagen solutions - Junhong Xie; Li Feng; Fanghui Deng; Wei Yue; Wei Liang; Qiannan Zhao; Wentao Ma; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Hydrocolloids, 2026)

High-efficiency solar-driven photothermal membrane distillation via permeate-side interfacial heating - Qian Yu; Mengfei Xie; Rong Chen; Kuiling Li; Liqiu Zhang; Bo Pan; XueJun Pan; Junhui Zhang; Dan Qu (Desalination, 2026)

Improving spatial resolutions of unmanned aerial vehicle hyperspectral images to predict grain yield and protein content in rice - Zhonglin Wang; Rong Hu; Mingming Hu; Huilai Yin; Tao Liu; Yufei Xie; Yangming Ma; Feng Yang; Feijie Li; Zhiyuan Yang; Yongjian Sun; Jun Ma (Precision Agriculture, 2026)

Exploring spinal degenerative diseases therapy targets through druggability genes: a Mendelian randomization study - Hao Qin; Mingyu Hao; Zhitan Wang; Jing Zhang; Minghao Xie; Yuhang Diao; Xiaojun Hu; Hongtao Rong; Tao Zhu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Nutrient input strategies mediate the link of rhizosphere soil microbiomes with rice productivity: Based on a decade-long field experiment - Ning Su; Xiangmin Rong; Qiaorong Li; Yansong Xiao; Guixian Xie; Chang Tian; Yali Kong; Yuping Zhang; Gongwen Luo (Agriculture, Ecosystems & Environment, 2026)

Novel prenylated diketopiperazines with anti-osteoclastogenic activity from the deep-sea-derived Penicillium limosum ZEN48 - Yong Zhang; Yan-Qing Guo; You Li; Zheng-Biao Zou; Zhe-Wen Chen; Rong Zhao; Robert J. Capon; Tai-Zong Wu; Chun-Lan Xie; Xian-Wen Yang (Marine Life Science & Technology, 2026)
A systematic chemical investigation of the deep-sea-derived fungus Penicillium limosum ZEN48 resulted in the isolation of four new indole-diketopiperazine alkaloids, limopiperazines A–D ( 1 – 4 ), alongside 16 known analogues ( 5 – 20 ). The structures of the new compounds were determined through comprehensive spectroscopic analysis, quantum chemical calculations, X-ray crystallography, and biogenetic considerations. Limopiperazine C ( 3 ) potently inhibited osteoclast differentiation and disrupted actin ring formation. Integrated RNA sequencing, RT-qPCR and molecular docking revealed that limopiperazine C exerts the anti-osteoclastogenic effect by modulating the ferroptosis signaling pathway via targeting heme oxygenase-1 (Hmox-1), positioning it as a promising lead compound for developing anti-osteoporotic agents.

Unraveling the phototransformation of 2,4,6-tribromophenol: Aqueous mechanisms involving ·OH and the emergence of hydroxylated PBDEs - Junling Ma; Muhammad Zeshan; Rong Cao; Hong-bin Xie; Ningbo Geng; Haijun Zhang; Yuan Gao; Lidong Wu; Jiping Chen (Water Research, 2026)

A germline-specific vesicular structure licenses mRNA activation during spermiogenesis and is hijacked in gastric cancer - Mingxi Liu; Zerui Wang; Yinuo Li; Qingsong Xie; Zhuang Xiao; Xuezhi He; Guanxiong Wang; Yang Gao; Yini Zhang; Lin Zheng; Xun Xia; Lujie Chen; et al. (Science Bulletin, 2026)

Cadmium exposure and cognitive impairment in middle-aged and older adults: Linking neurocognitive deficits with systemic inflammation - Rong Ma; Zhentao Gao; Runhua Wang; Yixuan Wu; Wei Hu; Fang Pei; Jixin Tang; Linshen Xie; Kangguang Lin; Xiaojiang Tang (NeuroToxicology, 2026)

Release kinetics and environmental risks of TCPP from polyurethane foam microplastics: Insights from artificial seawater to natural estuarine water - Shan-Shan Yao; Yu-Han Xie; Zhi-Yan Wang; Shan Liu; Rui Hou; Lang Lin; Yu Zhong; Xiao-Ping Huang; Heng-Xiang Li; Xiang-Rong Xu (Environmental Pollution, 2026)

Efficient fabrication of PLA/PBAT/ZnO films with inverted-pyramid Micro/nanostructures for robust anti-wet pack and antimicrobial protection - Yu Du; Rong Zhou; Kai Mu; Congyuan Zhang; Changjun Guo; Jiabao Lu; Zihao Li; Heng Xie; Ting Wu; Jinping Qu (Chemical Engineering Journal, 2026)

Quercetin suppresses the proliferation of thyroid cancer cells by reducing the expression level of DPP4 and inhibiting its enzyme activity - Jie Xu; Jian Huang; Rong Zou; Yuliang Deng; Hong Xie; Wanqiu Huang; Zhaoqi Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Mechanisms by Which Humic Acid Reduces Copper Toxicity in Citrus Roots Based on Omics and Physiology - Wei-Tao Huang; Rong-Rong Xie; Liang-Yuan Tong; Tian-Tian Xia; Jiuxin Guo; Ning-Wei Lai; Zeng-Rong Huang; Lin-Tong Yang; Li-Song Chen (Journal of Plant Growth Regulation, 2026)

The causal relationship between polycystic ovary syndrome and structural changes in brain: a Mendelian randomization study - Han Yang; Wei Xie; Camilo Alberto Pinzon Galvis; Si Huang; Xu He; Si-yi Yu; Qing You; Fan-rong Liang; Zhi-yong Xiao; Ning Li (Brain Imaging and Behavior, 2026)

Design, synthesis, characterization and exploration of anti-HBV activity of matrine-adenine hybrids - Meng-Fan Xie; Zhou-Fei Zheng; Jing-Lei Wang; Rong-Tao Li; Zhi-Jun Zhang (Molecular Diversity, 2026)

Seneca Valley virus 2B and 3 C proteins attenuate the cGAS-STING signaling pathway by targeting STING for degradation - Xuexia Wen; Meijun Zhou; Shijie Xie; Jin Yuan; Yu Hong; Ruiyi Ma; Liwei Zhao; Dan Wang; Rong Quan; Peipei Cheng; Jiangwei Song (Veterinary Microbiology, 2026)

Bridging cortical intentions: brain–computer interfaces for spinal cord injury recovery - Xuantao Hu; Jiale He; Na Li; Jian Mo; Senyu Yao; Yubao Lu; Mudan Huang; Pan Jiang; Mao Pang; Lei He; Jin Gong; Zifeng Liu; et al. (Science Bulletin, 2026)

Synthesis of novel aminomethyl phosphinic acid extractants and their use in the extraction and separation of zirconium and hafnium - Meiying Xie; Fan Yang; Rong Liu; Luyao Yang; Jinming Du; Xinyuan Lan; Minzhong Huang (Hydrometallurgy, 2026)

Evaluation of near infrared spectroscopy for direct detection of common microplastics contamination in camel Milk powder - Chunxu WAN; Yin LIU; Jing XIE; Feng CHEN; Huijie SHEN; Rong LI (Food Chemistry, 2026)

Using integrated multi-omics and molecular docking to decode stone epiphytic culture as a strategy for enhancing flavonoids and bioactivity in Dendrobium officinale leaves for functional tea development - Jing Li; Rong Zhou; Yingyue Hou; Yichang Chen; Shaohao Xie; Jinyu Wu; Jiang Chen; Hongbin Hou; Guangying Du (Food Bioscience, 2026)

Achieving sustainable rice production with reduced nitrogen fertilization through unlocking soil organic nitrogen mineralization by alleviating microbial carbon limitation - Ning Su; Xiangmin Rong; Yao Liu; Junru Li; Runjia Yin; Guixian Xie; Yuping Zhang; Gongwen Luo (Field Crops Research, 2026)

Towards sustainable potato production in China: Optimizing nitrogen and water management with 5R strategies - Zhaolong Pan; Rong Jiang; Daijia Fan; Daping Song; Hanyou Xie; Xiya Wang; Wei Zhou; Ping He; Wentian He (European Journal of Agronomy, 2026)

Sustained performance and microbial succession in novel artificial rumen system coupling dynamic membrane with methanogenic granules for acid absorption - Xiang-Lin Chang; Bao-Shan Xing; Yu Qin; Juan Xie; Zhi-Bo Li; Xiaochang C. Wang; Rong Chen; Yu-You Li (Bioresource Technology, 2026)

A novel deep neural network with geographical position constraints for shallow water depth estimation - Xinle Guo; Rong Huang; Yusheng Xu; Bin Cao; Kuifeng Luan; Zhen Ye; Huan Xie; Xiaohua Tong (Marine Geodesy, 2026)

A scalable human liver-on-a-chip platform for predictive safety assessment - Gauri Kulkarni; Lizao Chen; Jing Sang; Ji Hye Seo; Romain Grall; Yunfang Wang; Paige Gilbride; Yu-Chieh Yuan; Matthew Albaum-Getzen; Jenna McCormack; Jingzhe Ma; Alyssa Fanelli; et al. (Toxicology, 2026)

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

A low pH level in ripening pear tissue promotes the growth and pathogenicity of Alternaria alternata by causing ammonia accumulation and alkalization - Meiqi Gao; Rong Li; Yanxia Zhang; Puwei Yan; Xiwang Wang; Yue Xie; Miao Zhang; Yongcai Li (Physiological and Molecular Plant Pathology, 2026)

Elucidating the role of overlooked environmentally persistent free radicals and reactive chlorine species on photoaged chlorine-containing microplastics: New insights into formation mechanisms and health risks - Linyang Xie; Jingbo Ling; Kaiyou Huang; Jianyu Lin; Hongjian Li; Zhiyu Zhou; Shixiang Gao; Rong Ji; Cheng Gu; Dongmei Zhou; Xueyuan Gu (Journal of Hazardous Materials, 2026)

Mechanism of macrophage mitochondrial transfer in CBNPs induced EndMT of pulmonary microvascular endothelial cells - Mengruo Wang; Qian Wang; Qingping Liu; Shanshan Zhang; Yujia Xie; Tao Zhang; Ze Yang; Lei Bao; Yaxian Pang; Dongxing Shi; Jiaji Cheng; Yujie Niu; et al. (Journal of Hazardous Materials, 2026)

One stone, two birds: Preparation of nutritionally fortified and easy-to-swallow 3D printed pea protein gel based on high internal phase emulsions - Wei Liang; Junhong Xie; Qiannan Zhao; Chenghong Jiang; Xiaofeng Zhan; Mingrong Chen; Lu Zhang; Chuan Li; Jianhua Rong; Yang Hu (Food Hydrocolloids, 2026)

Adaptive variational fusion of multi-source lunar digital elevation models based on curvature regularization - Siyi Qiu; Zhen Ye; Yusheng Xu; Jia Qian; Rong Huang; Tao Tao; Huan Xie; Xiaohua Tong (Computers & Geosciences, 2026)

Monodisperse lutetium-177-labeled poly(lactic acid) microspheres for radioembolization therapy of hepatocellular carcinoma - Qing-Rong Jiang; Ping He; Ling-Yun Guo; Qi-Yi Mo; Xing-Long Zhou; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Wen-Jie Zhang; Xiao-Jie Ju; Liang-Yin Chu (Chemical Engineering Journal, 2026)

Study of the machine learning emission inversion method of the CUACE model on the basis of fused Fengyun observations - Tao Niu; Congwu Huang; Yiliang Jiang; Qi Jiang; Bihui Zhang; Hongli Liu; Rong Li; Yuzhan Xie; Tijian Wang (Atmospheric Pollution Research, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

Jinxinkang Granule Preserves Myocardial Function by Suppressing Cardiac Senescence Through the cGAS-STING Axis in a Pressure Overload Mouse Model of Heart Failure - Jingping Sun; Kang Xie; Yingxie Cao; Liang Kang; Rong Li (Cardiovascular Toxicology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Impact of complex inhibitors in straw hydrolysates on xylose-fermenting Saccharomyces cerevisiae and inhibitor-tolerant strain construction - Xue-Xue Ji; Bo Li; Rong-Rong Chen; Zi-Yuan Xia; Cai-Yun Xie; Yue-Qin Tang (Fungal Biology, 2026)

Phthalocyanine-based prodrug with H₂S-triggered domino cascade for photodynamic and multiple-mechanism synergistic anti-metastatic therapy - Mengyu Yao; Qi-Qi Yang; Huang-Hao Tang; Xue-Yan Li; Wei Xie; Chao Wang; Song Yang; Xingshu Li; Mei-Rong Ke; Jian-Dong Huang (Chemical Engineering Journal, 2026)

Fine-tuning Atmospheric Parameters for Improving ENSO Simulation in the Zebiak–Cane Model - Xiaojun Wei; Lin Chen; Ming Sun; Ruihuang Xie; Rong-Hua Zhang (Advances in Atmospheric Sciences, 2026)

Predicting the occurrence of the emerging disinfection byproducts halocyclopentadienes and analyzing their driving factors in nationwide tap water using machine learning - Yongchang Xie; Quanzhen Liu; Tianhao Liu; Lihua Lin; Rong Li; Chuan Du; Wenru Bian; Donghong Wang (Water Research, 2026)

Corrigendum to “Carbon sink potential and planning and governance strategies of ecological space in megacities: A case study of Beijing” [Sustainable Cities and Society 136 (2026) 12/107036] - Qiwen Cao; Aman Zhang; Rong Cong; Dan Zhao; Xiaochun Huang; Shanshan Ning; Xiaoran Xie (Sustainable Cities and Society, 2026)

Carbon sink potential and planning and governance strategies of ecological space in megacities: A case study of Beijing - Qiwen Cao; Aman Zhang; Rong Cong; Dan Zhao; Xiaochun Huang; Shanshan Ning; Xiaoran Xie (Sustainable Cities and Society, 2026)

Co-reduction of nitrogen and phosphorus fertilizer inputs reduced nutrient losses and maintained crop yield in a rice-oilseed rape rotation system - Haodong Zhang; Ning Su; Gongwen Luo; Zhi Peng; Xizhe Luo; Sihai Qin; Mengjiao Huang; Chang Tian; Xiangmin Rong; Guixian Xie; Jun Xie (Soil and Tillage Research, 2026)

Preharvest melatonin application enhances soft rot resistance in kiwifruit through the jasmonic acid signaling pathway - Junsen Peng; Shufeng Du; Rong Fan; Youhua Long; Guofang Xie; Xiaochun Ding; Xiaoqing Dong (Postharvest Biology and Technology, 2026)

Magnesium deficiency limits electron transport efficiency and photosynthesis, and induces oxidative stress in tobacco - Rong-Rong Xie; Jingjuan Gao; Changzheng Wu; Jinping Guo; Qian Cheng; Hailu Wang; Tinmin Liang; Jianjun Lu; Chaoyuan Zheng; Liangquan Wu; Li-Song Chen; Songbiao Chen; et al. (Plant Science, 2026)

Nighttime lights-based downscaling for high-resolution electricity mapping: Insights into consumption, efficiency and footprint for sustainable energy management - Pan Zhang; Yongyang Wang; QiangQiang Rong; Yulei Xie (Journal of Cleaner Production, 2026)

Risk assessment and environmental influencing factors of urinary polycyclic aromatic hydrocarbons metabolites in pregnant women in Zunyi, China - Jing Yang; Jing Jiang; Linfei Wu; Pei Xu; Nian Wu; Rui Yu; Yanling Xiao; Xingting Zheng; Rong Zeng; Yuanzhong Zhou; Yan Xie; Xubo Shen (Journal of Environmental Sciences, 2026)

Rare earth element hyperaccumulation in vascular plants: Occurrence, mechanisms, and applications - Ruo-Rong Liu; Cui-Ling Huang; Hong-Xiang Zheng; Chong Liu; Rui-Qi Zhang; Yue Cao; Antony van der Ent; Can-Die Xie; Wen-Shen Liu; Jean Louis Morel; Catherine Sirguey; Damien Blaudez; et al. (Critical Reviews in Environmental Science and Technology, 2025)

Release kinetics and bioaccessibility of heavy metal from antifouling paint particles in simulated digestive fluids: An emerging threat to marine biota - Zhen-Liang Li; Ting-Ting Xu; Shan-Shan Yao; Heng-Xiang Li; Shan Liu; Rui Hou; Lang Lin; Zhi-Xin Ni; Qun Xie; Xiao-Ping Huang; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

Optimizing Mytilus edulis and Gracilaria lemaneiformis ratios for maintaining water environment stability in IMTA systems - Ruixue Tong; Rong Zhang; Jinghui Fang; Yitao Zhang; Jialei Xu; Xiaowen Zhang; Yumeng Xie (Marine Pollution Bulletin, 2025)

Bioactive constituents from Salacia obovatilimba as potential in vitro hSGLT2 inhibitors - Zhi-Yong Jiang; Lin Chen; Hong-Xi Xie; Jun-Jie Hao; Rong Chen; Chun-Qiu Huang; Hong-Lei Zhang; Ai-Xue Zuo (Phytochemistry, 2025)

Oyster-mussel differences in cadmium accumulation linked to molecular weight distribution of Cd-binding proteins - Guangbin Zhong; Xue Cao; Sen Du; Canchuan Zhang; Li Zhang; Niklas Helle; Minwei Xie; Rong Chen; Qiao-Guo Tan (Journal of Hazardous Materials, 2025)

State-selective engineering in luminescent metal-organic frameworks: Ligand-to-ligand charge transfer activates superior photocatalytic sterilization in Wei River - Liang Qiu; Yajie Zhang; Baiyu Wu; Wenqiong Liu; Yiwen Xie; Jing He; Kerang Huang; Jianlong Wang; Rong Wang (Journal of Hazardous Materials, 2025)

Sonodynamic interfacial-assisted photosensitizer disrupts lipid bilayer order to eradicate gram-negative bacteria using HB@ZIF-8 nanoparticles - Li Ding; Yiwen Xie; Xinrui Bai; Liang Qiu; Yerlan Zharykbasov; Zhainagul Kakimova; Gang Wu; Jianlong Wang; Yuxia Song; Rong Wang (Food Chemistry, 2025)

Milk-derived exosomes in breast cancer therapy: Mechanisms and therapeutic potential - Deju Zhang; Shunjia Xing; Chengyuan Wang; Xinyao Wang; Yaqi Rong; Yiming Gan; Xuanyu Yang; Ni Xie (Food Bioscience, 2025)

Acoustic emission-based damage assessment and failure mechanism analysis on CFST columns with different joint configurations under compression-bending loads - Enchao Rong; Junfu He; Liqiang Tang; Kaizhong Xie; Yanjun Chang (Engineering Structures, 2025)

Development and validation of a magnetic - based corrosion detection system for reinforced concrete structures - Jian Cheng; Yu-meng Xie; Rong-sen Gao; Ye Tian; Guo-yi Zhang; Dongming Yan; Bo Chen; Ruo-yi Zhao; Bei Li; Jun Chen; Dong-yang Cai; Wei-qiang Wu; et al. (Engineering Structures, 2025)

Upcycling plastic waste into high-value gases via pulsed joule heating for economic and carbon benefits - Zitong Wan; Xuan Xie; Yunfeng Ma; Guohua Zhu; Rong Jin; Bingcheng Lin; Minghui Zheng (Chemical Engineering Journal, 2025)

An electrochemical reactor that enables continuous and uniform flow of high-viscosity slurry for semi-solid flow batteries - Chao Deng; Xiaoxin Li; Furong Xie; Miguel A. Modestino; Mustafa Kemal Bayazit; Barun Kumar Chakrabarti; Jeffrey Gostick; Zinan Wu; Rong Chen; Guo-Ming Weng (Chemical Engineering Journal, 2025)

Correction: Regulatory effect of AMP-activated protein kinase on pulmonary hypertension induced by chronic hypoxia in rats: in vivo and in vitro studies - Xiaoying Huang; Rong Fan; Yuanyuan Lu; Chang Yu; Xiaomei Xu; Xie Zhang; Panpan Liu; Shuangquan Yan; Chun Chen; Liangxing Wang (Molecular Biology Reports, 2025)

Development of a Phage‐Display Derived Peptide‐Based Colloidal Gold Strip for Rapid Detection of Enterocytozoon hepatopenaei via Spore Wall Protein Interaction - Jia‐rong Xie; Hao Li; Ben Chen; Yan‐chang Fan; Yu‐hao Gong; Liqun Lu (Journal of Fish Diseases, 2025)
Infection by Enterocytozoon hepatopenaei (EHP) leads to stunted or arrested growth in shrimp, causing significant economic losses in shrimp aquaculture. In this study, the spore wall protein EhSW12 was expressed using a prokaryotic expression system. Subsequently, phage display technology was employed to screen for peptides that interact with EhSW12. A rapid detection method was developed that bypasses the laborious procedure of extracting tissue DNA samples. Instead, enzymatic digestion was used to lyse the spore wall protein present in tissue homogenates, thereby enabling direct detection of EhSW12 via antigen colloidal gold rapid test strips and dot blot assays. The colloidal gold test strips, noted for their convenience and rapidity, satisfy the requirements for on‐site testing, while the dot blot method—with its simple operation—is well suited for high‐throughput sample analysis. Both methods were compared with the national standard qPCR assay. Specificity was validated using various shrimp antigens prepared in the laboratory; the results demonstrated that only the EHP antigen yielded a positive reaction, with no cross‐reaction observed with other common shrimp pathogens (e.g., white spot syndrome virus, decapod iridescent virus and highly pathogenic Vibrio ). Sensitivity tests indicated that the minimum detection limits for the test strip and dot blot methods were, respectively, 7 × 10 6 copies and 5.2 × 10 4 copies. In summary, both methods exhibit strong specificity, high sensitivity, rapid detection speed and operational simplicity—characteristics that make them highly suitable for large‐scale on‐site rapid testing.

Concentration-dependent visual SO2 detection from trace to pure in a zirconium MOF - Guang-Rui Si; Xiang-Jing Kong; Lin-Hua Xie; You-Tuo Zhang; Tao He; Jian-Rong Li (Science Bulletin, 2025)

Functional insights into avrPto5 from Pseudomonas syringae pv. actinidiae and its interaction with zinc finger proteins regulating plant defenses - Muhammad Asif; Ting Xie; Rong Fan; Youhua Long; Zhibo Zhao (Physiological and Molecular Plant Pathology, 2025)

Hydrothermal carbonization: A potent strategy for simultaneously eliminating ARGs-associated pollutants in livestock manure and blocking ARGs horizontal gene transfer - Sunlin Chi; Jinmei Xiao; Jinying Xu; Aijing Li; Jianhui Hu; Xinyi Wang; Meiyan Zhang; Wei Liu; Yalan Zhang; Huijun Ding; Jun Rong; Li Leng; et al. (Journal of Hazardous Materials, 2025)

Hypocalcemia as biological mechanism responsible for prenatal exposure to polycyclic aromatic hydrocarbons (PAHs) and anemia: Insights from Zunyi birth cohort - Lei Luo; Wenbi Yang; Haonan Zhang; Lei Bai; Zhongbao Chen; Lin Tao; Haiyan Wang; Shimin Xiong; Ruoxuan Li; Yijun Liu; Xingyan Liu; Yan Xie; et al. (Journal of Environmental Sciences, 2025)

Enhancing Lithium extraction via ionic liquid coupled electrochemical methods - Xinyuan Lan; Rong Liu; Liyan Xue; Minzhong Huang; Meiying Xie; Hongye Wang; Hao Zhang; Fan Yang (Hydrometallurgy, 2025)

Caulerpa lentillifera extract alleviates the chronic diquat-induced liver oxidative damage in zebrafish (Danio rerio) in association with Nrf2 and AMPK/mTOR signaling pathway - Xiang Lin; Xiaocen Xie; Qijun Fu; Zhongqun Liu; Ye Xiao; Yongqiang Wang; Haiping Li; Xi Xie; Rong Wang; Yingxia Zhang; Yanting Song; Wenting Hu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Simulating the multiple effects of a diatom bloom on metal bioaccumulation in clams - Weiyi He; Fengjie Liu; Minwei Xie; Rong Chen; Qiao-Guo Tan (Marine Pollution Bulletin, 2025)

Exploring the mechanism of volatile organic compounds in respiratory tract tumors based on network toxicology and molecular simulation - Ran Ding; Qi Quan; QianQian Dai; TingQiu Quan; Rong Huang; DeHuan Xie; ZhiQing Long (Science of The Total Environment, 2025)

Navigating the lunar frontier: one hundred landing sites at the south pole for future mission challenges - Yongjiu Feng; Pengshuo Li; Haoteng Li; Yan Liu; Mengrong Xi; Rong Wang; Shurui Chen; Panli Tang; Yuze Cao; Qian Huang; Qionghua You; Shijie Liu; et al. (Science Bulletin, 2025)

Selective flotation separation of smithsonite and calcite using sodium dodecyl phosphonate as a collector: Flotation performance and adsorption characteristics - Zehang Guo; Haiyang He; Peilun Shen; Rong Peng; Haiyun Xie; Dianwen Liu (Minerals Engineering, 2025)

Bicarbonate ions enhanced surface Fe(II) regeneration and peroxymonosulfate activation on stainless-steel scrubber cathode for BPA degradation - Danni Deng; Rong Chen; Qianqian Zhong; Binbin Xiong; Jia Deng; Na Zhang; Shiwei Xie (Journal of Water Process Engineering, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Refining marine metal biomonitoring through insights into allometry in green mussels - Yuqing Liao; Haiyan Xiong; Wenze Xiao; Jun Liu; Minwei Xie; Rong Chen; Qiao-Guo Tan (Environmental Pollution, 2025)

Unraveling the source-terminal PAH pollution from coal chemical wastewater in the Yellow River Basin via molecular fingerprint concentration analysis - Rong Li; Quanzhen Liu; Xiong Xu; Yongchang Xie; Lihua Lin; Mengru Yang; Donghong Wang (Environmental Pollution, 2025)

Crystalline water pre-embedding and defect engineering endows V6O13 with enhanced Zn2+ ions storage - Fangan Liang; Zhengguang Zou; Rong Zheng; Zhuojia Xie; Lijie Song; Yunjie Wang (Chemical Engineering Journal, 2025)

In-situ construction of Bi0-BiOCl with oxygen vacancies on N-doped magnetic carbon microspheres for upgrading adsorption-photocatalysis synergy to degrade fluoroquinolone antibiotics in wastewater - Xiaoyan Xie; Yingying Liu; Xi Deng; Mei Luo; Yude Liu; Rong Wang (Chemical Engineering Journal, 2025)

Temporin-GHaR Peptide Alleviates LPS-Induced Cognitive Impairment and Microglial Activation by Modulating Endoplasmic Reticulum Stress - Da-Qi Zhang; Xiaoqian Dong; Simin Su; Linlin Zhang; Jiayu Zhang; Wenjing Yang; Wenting Hu; Lushuang Li; Yanting Song; Xi Xie; Qifu Li; Rong Wang; et al. (Probiotics and Antimicrobial Proteins, 2025)

STL-GT: graph-structured learning based transformer for GNSS positioning enhancement in urban environments - Zhenni Li; Xin Li; Qianming Wang; Rong Yuan; Xuesong Tan; Maodeng Li; Marios M. Polycarpou; Shengli Xie (GPS Solutions, 2025)

FKH domain-mediated nuclear FOXP3 suppresses gastric cancer malignancy via c-MYC/CDKN1A regulation, EMT inhibition, and PI3K/AKT signaling modulation - Yu Chen; Xia Zhao; Yuze Zhu; Ling Xu; Juanjuan Wang; Zheyi Chen; Hui Chen; Tingting Rong; Yanhui Ma; Yi Liu; Yunlan Zhou; Yingxia Zheng; et al. (Molecular and Cellular Biochemistry, 2025)

Anti-neuroinflammatory naphthol dimers from the marine-derived fungus Penicillium sp. HQ1-23 - Yuan-Han Xie; Chun-Hong Wang; Rong Wang; Hui Jia; Fei Liu; Zi-Hong Peng; Ya-Hui Zhang; Jun Li; Rui-Yun Yang; Li-Jun Zhang; Wei-Feng Xu (Phytochemistry, 2025)

Effects of aged microplastics on the abundance of antibiotic resistance genes in oysters and their excreta - Yifang Yu; Jing Qian; Weichao Wang; Minwei Xie; Qiao-Guo Tan; Rong Chen (Marine Environmental Research, 2025)

In Situ isotope tracing for metal bioaccumulation in open waters: Implications for interpreting biomonitoring data and safe seafood aquaculture - Haiyan Xiong; Tao Wang; Xue Cao; Jing Qian; Stuart L. Simpson; Rong Chen; Qiao-Guo Tan; Minwei Xie (Journal of Hazardous Materials, 2025)

H3K18 lactylation drives the progression of silica nanoparticles-induced pulmonary fibrosis via promoting macrophage M1 polarization - Lili Shi; Lin Zhang; Zhenfang Ma; Zhaohui Hu; Zihan Geng; Hao Liu; Jingyuan Wang; Ke Feng; Yiheng Geng; Yan Liu; Cunhui Zhang; Yujia Xie; et al. (Journal of Hazardous Materials, 2025)

Recovery of rare earth elements from sediments affected by mining activities - De-Xiang Xu; Xuan-Pu Cheng; Cui-Ling Huang; Xiao-Rui Liu; Can-Die Xie; Rong-Liang Qiu; Chang Liu; Mei-Na Guo; Jean-Louis Morel; Wen-Shen Liu; Ye-Tao Tang (Journal of Hazardous Materials, 2025)

The impact of the COVID-19 epidemic on anthropogenic emissions in the Beijing-Tianjin-Hebei region of China based on 3DVar sectoral emission inversion - Congwu Huang; Tao Niu; Tijian Wang; Mengmeng Li; Rong Li; Chaoqun Ma; Hao Wu; Yawei Qu; Hongli Liu; Xu Liu; Yuzhan Xie (Journal of Hazardous Materials, 2025)

Multifunctional microbial inoculation regulates compost product microbiomes, with implications for improving crop health and yield - Xin Liu; Xiangmin Rong; Pan Jiang; Junyan Yang; Han Li; Xingxiang Deng; Guixian Xie; Gongwen Luo (Journal of Cleaner Production, 2025)

The effects of transportation structural adjustment policy on carbon emission: Evidence from China - Qiaoya Xie; Yunqiang Wu; Rong Zhang (Journal of Cleaner Production, 2025)

Bundle adjustment for multi-source Mars orbiter imagery with generalized control constraints - Qionghua You; Zhen Ye; Chen Chen; Huan Xie; Yanmin Jin; Rong Huang; Changyou Xu; Yusheng Xu; Xiaohua Tong (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Evaluation of probiotic properties of lactic acid bacteria and physicochemical characteristics of fermented jujube (Ziziphus jujuba Mill.) polysaccharides - Rong Wang; Shufan Xie; Fei Li; Lanjian Qin; Jianming Ye; Jiaqi Chen; Xiao Yang; Yunlu Wei (Food Bioscience, 2025)

Machine learning-driven discovery of efficient narrow-band green phosphor for wide-color-gamut backlight displays - Shuifu Liu; Kunjie Song; Shuxing Li; Rong-Jun Xie (Chemical Engineering Journal, 2025)

Bio-organic fertilizer application improves cucumber growth, disease resistance, and soil fertility by regulating rhizosphere microbiomes - Junyan Yang; Xin Liu; Xiangmin Rong; Pan Jiang; Yixiang Xia; Guixian Xie; Gongwen Luo; Xiaoyuan Yan (Plant and Soil, 2025)

Integrative Approaches Identify Genetic Determinants of Levodopa Induced Dyskinesia - Ying Wan; Lu Rong; Qingyuan Li; Suzhi Liu; Wentao Li; Min Ye; Weifeng Luo; Anmu Xie; Jingsong Shao; Dengjun Guo; Xiaoping Zhang; Kezhong Zhang; et al. (Molecular Neurobiology, 2025)

From adhesion to destruction: minocycline's dual action against Cutibacterium acnes biofilms - Yuanyuan Xie; Xuesong Yang; Meng Zhou; Yuzhen Liu; Rong Zeng (Brazilian Journal of Microbiology, 2025)

Mechanical and micro-mechanical investigations of nano-SiO 2 and polypropylene fiber reinforced cement soil in marine environments - Zhilin Xiong; Qingsheng Chen; Gaoliang Tao; Sanjay Nimbalkar; Huiyang Rong; Kai Xie (Marine Georesources & Geotechnology, 2025)

Comprehensive assessment of various digestion protocols for extraction microplastics from organic-rich environmental matrices - Kaiyou Huang; Linyang Xie; Xueyuan Gu; Junying Xie; Jiapeng Li; Shixiang Gao; Rong Ji; Dongmei Zhou (Water Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

An energy-saving pH-asymmetric electrolyzer for simultaneous methane conversion and hydrogen production - Rong Chen; Furong Xie; Zinan Wu; Xiaoxin Li; Chao Deng; Zhenpeng Yao; Guo-Ming Weng (Science Bulletin, 2025)

Sophormodines A−C, three alkaloids with antiviral activities against the HBV from the seeds of the Tibetan medicine plant Sophora moorcroftiana - Ting-Ting Liu; Meng-Fan Xie; Qing-Qing Yang; Rong-Tao Li; Zhi-Jun Zhang (Phytochemistry, 2025)

Corrigendum to “Removal of antibiotic resistance from wastewater in aquatic ecosystems dominated by submerged macrophytes” [J Hazard Mater 489 (2025) 137706] - Rong-min Zhang; Xiao-jie Chen; Ya-fei Li; Hui-zhen Tan; Wen-qing Huang; Ling-lin Li; Xin-ting Li; Jie Xie; Yun-xiao Chong; Xin-lei Lian; Xian-hui Huang (Journal of Hazardous Materials, 2025)

Bridging the knowledge gap: From poly(butylene adipate-co-terephthalatebutylene) degradation to CO2-generating mineralization under the synergistic effect of bacteria and fungi - Yue Wang; Qi Liu; Chang-Hong Xie; Ruo-Tong Zhao; Qiu-Xiang Tang; Dong-Fei Han; Yi-Ning Xia; Ji-Xiao Cui; Chang-Rong Yan; Wen-Qing He (Journal of Hazardous Materials, 2025)

Pt decorated (CoMnFeCrNi)3O4 high-entropy oxide for low-temperature combustion of C3H8 - Lihong Xie; Yaohun Dun; Qiji Wang; Jie Xu; Song Li; Rong Chen; Chun Du; Bin Shan (Fuel, 2025)

Facile fabrication of ethyl cellulose/gelatin fibers incorporated with copper-based metal-organic frameworks as humidity-triggered release of carvacrol for blueberry preservation - Jing Xie; Xingyu Rong; Xiaoqian Jiang; Yuping Zhao; Tianhua Ding; Jing Yan; Suqing Li; Wen Qin; Mingrui Chen; Yaowen Liu (Food Chemistry, 2025)

The antibacterial activity, action mechanisms and prospects of Baicalein as an antibacterial adjuvant - Liuqing Mu; Kaiyan Xie; Rong Chen; Jiang Cao; Yang Shu; Xuebin Huang (World Journal of Microbiology and Biotechnology, 2025)

Evaluating the Impact of Transformation and Upgrading on the Green Efficiency of Industrial Water: Evidence from Sectoral Performance - Abderhim Ötkür; Qiangqiang Rong; Wencong Yue; Jianyu Zhang; Yulei Xie; Meirong Su (Water Resources Management, 2025)

Therapeutic potential of P2X7 receptor in retinal diseases - Min Wen; Qin Xu; Jinfeng Xie; Rong Wu; Xiaomei Chen; Nianlian Wen; Sheng Huang (Purinergic Signalling, 2025)

Mobile Genomic Island GEI-FN1A in Aeromonas salmonicida FN1 Contributes to the Spread of Antibiotic-Resistance Genes - Xinru Xie; Zhaorui Ren; Rong Wang; Kanglu Tian; Xindi Huang; Yang Lyu; Guangxiang Cao; Jiafang Fu (Current Microbiology, 2025)

Dose-response pattern of marine macroalgae Gracilariopsis heteroclada to three fluoroquinolones and the cause-effect relationship of dose, growth, toxicity and sorption - Kun Lin; Youyou Guo; Rong Xin; Enyi Xie; Xuefeng Wang; Jianjun Cui; Jinhui Wu; Zhaowei Huang; Yong Liu; Shaoliang Lyu; Sipan Wang; Yongjian Huang; et al. (Algal Research, 2025)

Shellfish-macroalgae IMTA maintaining water environment stability: A case study of Crassostrea gigas and Gracilaria lemaneiformis IMTA in Sanggou Bay of China - Ruixue Tong; Rong Zhang; Jinghui Fang; Yitao Zhang; Jialei Xu; Xiaowen Zhang; Yumeng Xie (Marine Pollution Bulletin, 2025)

Urban flooding risk assessment and mitigation strategies based on optimal allocation of low impact development facilities - Fan Wen; Qiangqiang Rong; Zhihui Gu; Yulei Xie; Meirong Su (Sustainable Cities and Society, 2025)

Associations between serum trace elements and biological age acceleration in the Chinese elderly: A community-based study investigating the mediating role of inflammatory markers and the moderating effect of physical activity - Yan Wang; Wenyuan Zhu; Tao Zhang; Qingping Liu; Mengqi Zou; Yujia Xie; Mengruo Wang; Tian Shuai Wang; Yaxian Pang; Tao Jing; Rong Zhang (Journal of Hazardous Materials, 2025)

Degradation of biodegradable plastic films in soil: microplastics formation and soil microbial community dynamics - Yue Wang; Run-Hao Bai; Qi Liu; Qiu-Xiang Tang; Chang-Hong Xie; Aurore Richel; Christophe Len; Ji-Xiao Cui; Chang-Rong Yan; Wen-Qing He (Journal of Hazardous Materials, 2025)

Colloid phosphorus transport in agricultural soils: a critical review of content characteristics, migration mechanisms, and environmental drivers - Wen-Jing Liu; Man-Tong Luo; Rong-Liang Qiu; Ke-Tan Xie; Xin-Xian Long (Journal of Environmental Management, 2025)

Hydrodynamic perturbations on contaminant behavior in low-permeability sediments: porewater metal dynamics and risk assessment implications - Ning Wang; Hongwei Hu; Wenze Xiao; Qiao-Guo Tan; Rong Chen; Minwei Xie; Stuart L. Simpson (Environmental Pollution, 2025)

Single and joint associations of exposure to polycyclic aromatic hydrocarbons with hypertensive disorders of pregnancy: A nested case-control study - Rui Yu; Cheng Chen; Mingyu Deng; Nian Wu; Yanling Xiao; Songlin An; Lin Tao; Xingting Zheng; Jing Yang; Zhongmei Hu; Pei Xu; Xingyan Liu; et al. (Environmental Pollution, 2025)

Tuning ligand defect in porphyrins metal-organic frameworks to boost electrochemiluminescence for sensitive detection of amyloid-β1-42 - Jinyan Li; Xiaoqi Pei; Rong Qu; Lei Liao; Wen Zhang; Zhen Wang; Gang Xie; Sanping Chen; Jing Han (Chemical Engineering Journal, 2025)

Type-A and -C response regulator genes positively impact rice plant height and panicle architecture - Chenyu Rong; Renren Zhang; Jing Xie; Jieru Li; Tiantian Yan; Ziyu Liu; Yuexin Liu; Ruihan Xu; Xi’an Shi; Xuebin Zhao; Jiali Song; Yayi Meng; et al. (Plant Cell Reports, 2025)

Characteristics of loess landslides under the effects of faults and rivers and their correlations with geological and surficial evolutionary processes - Qi-qi Liu; Wan-li Xie; Hui Yang; Ming Yan; Rong-sen Zhu; Ke Mu; Yi-lun Chang; Shengjie Di; Xiaoliang He; Xiaomin Liu; Ying Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Effective feature matching of high-resolution planetary orbiter images based on optimized image partitioning and rapid local correspondence - Lin Xue; Zhen Ye; Dayong Liu; Shijie Liu; Rong Huang; Huan Xie; Yongjiu Feng; Beibei Guo; Yusheng Xu; Xiaohua Tong (Planetary and Space Science, 2025)

Assembly processes of rare and abundant microbial taxa are closely related to bacterial and fungal functionality during desert vegetation reestablishment - Zhouchang YU; Wei ZHANG; Pian DUO; Ying ZHANG; Xingfang TIAN; Lin SUN; Yuzheng GU; Junhong ZHANG; Jiaxing SONG; Ahejiang SAILIKE; Yujie LIANG; Rong FU; et al. (Pedosphere, 2025)

Mixture of experts leveraging Informer and LSTM variants for enhanced daily streamflow forecasting - Zerong Rong; Wei Sun; Yutong Xie; Zexi Huang; Xinlin Chen (Journal of Hydrology, 2025)

Removal of antibiotic resistance from wastewater in aquatic ecosystems dominated by submerged macrophytes - Rong-min Zhang; Xiao-jie Chen; Ya-fei Li; Hui-zhen Tan; Wen-qing Huang; Ling-lin Li; Xin-ting Li; Jie Xie; Yun-xiao Chong; Xin-lei Lian; Xian-hui Huang (Journal of Hazardous Materials, 2025)

Structural evaluation and formation regularities of garlic clove-like meat in prefabricated grass carp - Qin Yang; Junhong Xie; Yuting Zhang; Yiling Tian; Liang Song; Yongqiang Zhao; Jian Xiong; Ru Liu; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Chemistry, 2025)

Manipulating molecular conformation of charge-transfer cocrystal for NIR-II absorption and light/thermal-responsive imaging - Yun Rong; Si-Qi Chen; Yu Dong Zhao; Sheng Zhuo; Yuan-Yuan Li; Jin-Zhuo Liu; Yi-Yi Ju; Yue-Min Xie; Liang-Sheng Liao; Ming-Peng Zhuo; Ke-Qin Zhang (Chemical Engineering Journal, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Recruitment of copiotrophic and autotrophic bacteria by hyperaccumulators enhances nutrient cycling to reclaim degraded soils at abandoned rare earth elements mining sites - Yong-He Han; Xi-Wen Cui; Hai-Yan Wang; Xiao-Bin Lai; Ying Zhu; Jia-Bing Li; Rong-Rong Xie; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Hazardous Materials, 2025)

Secondary scattering shape from shading for precise terrain reconstruction of the lunar permanently shadowed regions - Jia Qian; Zhen Ye; Siyi Qiu; Rong Huang; Huan Xie; Yusheng Xu; Xiaohua Tong (Icarus, 2025)

Different atmosphere anneals modulation Au size increasing Au-TiO2 interaction boosting photogenerated carrier separation efficiency to enhance photocatalytic hydrogen evolution - Zheyuan Fan; Yiqiao Wang; Ruonan Hou; Rong Zhong; Yu Xie; Lianjun Liu; Yun Ling (Fuel, 2025)

Microbial interactions between Lactoplantibacillus plantarum and Rhodotorula mucilaginosa in the fermented fish juice system - Xiayin Ma; Bingqian Zhou; Lina Jiang; Mingyang Xie; Zhixing Rong; Shixian Yin; Faxiang Wang; Yongle Liu; Xianghong Li (Food Research International, 2025)

[1H-13C]-NMR-Based Metabolic Kinetics Reveals Brain Neurochemical Alterations in Mice After Retinal Ischemia–Reperfusion Injury - Guojing Lu; Rong Huang; Siyu Zeng; Yiqiao Xing; Hang Xie; Lei Du (Molecular Neurobiology, 2025)

SIRT5: a potential target for discovering bioactive natural products - Yuwei Xie; Nali Cai; Xiaohua Liu; Liangliang He; Yiming Ma; Changyu Yan; Juan Liang; Shu-Hua Ouyang; Ao Luo; Yingzhi He; Jun Lu; Dang Ao; et al. (Journal of Natural Medicines, 2025)
Silent information regulator 5 (SIRT5) is the fifth member of the sirtuin family, which is mainly expressed in mitochondrial matrix. SIRT5 plays a key role in metabolism and antioxidant responses, and is an important regulator for maintaining intracellular homeostasis. Given its involvement in multiple cellular processes, dysregulation of SIRT5 activity is associated with a variety of diseases. This review explores the structural characteristics of SIRT5 that influence its substrate specificity, highlights recent research advances, and summarizes its four key enzymatic activities along with their corresponding substrates in disease contexts. We also discuss the natural products that modulate SIRT5 activity and identify potential targets of SIRT5 through virtual docking, which may provide new therapeutic avenues. Although the mechanism of SIRT5 in diseases needs to be further elucidated and deglutathionylation activities are still at an early stage, targeting SIRT5 and its substrates holds significant promise for the development of novel therapeutics. Graphical abstract

First report of Colletotrichum siamense causing anthracnose on Evodia rutaecarpa in Hunan, China - Mengshan Sun; Jin Xie; Liu Cai; Rong Song; Li Zhou (Journal of Plant Pathology, 2025)

Promising amide acid modified monolayer graphene for simulating the ultraefficient separation of 90Sr2+ from 137Cs+ - Rong Liu; Luyao Yang; Meiying Xie; Fan Yang (Journal of Water Process Engineering, 2025)

Chemical composition, rheological properties and calcium-induced gelation mechanism of Premna microphylla Turcz polysaccharide - Weiqi Fei; Liyuan Rong; Xin Qi; Xinyu Lv; Jun Chen; Huiliang Wen; Jianhua Xie (Food Hydrocolloids, 2025)

Synergetic “amine scissors” break down cured epoxy resins with nearly 100% degradation efficiency - Furong Xie; Rong Chen; Chao Deng; Xiaoxin Li; Huiyan Yang; Yu Xie; Song Wang; Guo-Ming Weng (Chemical Engineering Journal, 2025)

Narrow-band green nitride phosphor for wide color gamut backlighting - Xinyu Zhang; Wanyuan Li; Chao Wang; Lin Zhang; Shuxing Li; Rong-Jun Xie (Chemical Engineering Journal, 2025)

1DCNN-based prediction methods for subsequent settlement of subgrade with limited monitoring data - Sen-Lin Xie; Anfeng Hu; Meihui Wang; Zhi-Rong Xiao; Tang Li; Chi Wang (European Journal of Environmental and Civil Engineering, 2025)

A novel pretreatment process for vanadium extraction: Purification and recovery of negative component calcium in vanadium-bearing steel slag - Guohua Ye; Yun Zhang; Yu Xie; Xinyue Xiang; Yiyang Rong; Changxu Song (Process Safety and Environmental Protection, 2025)

Pasting, structural properties, and in vitro digestibility of water chestnut (Eleocharis dulcis Burm. f., Cyperaceae) starch co-gelatinized with different hydrocolloids - Xinyu Lv; Liyuan Rong; Weidong Zhang; Huiliang Wen; Mingyue Shen; Xin Qi; Jiajun Song; Jianhua Xie (Food Hydrocolloids, 2025)

Decade-long successive biochar amendment enhances wheat production and increases crop system resistance to unfavorable meteorological factors - Zhe Chen; Penghui Jin; Qi Liu; Yanhui Zhang; Tianlong Hu; Hui Wang; Rong Zhou; Jingru Zhang; Xingwu Lin; Zubin Xie (Field Crops Research, 2025)

Hidden threat in turbid waters: Quantifying and modeling the bioaccumulation and risks of particulate metals to clams - Jing Qian; Xue Cao; Haiyan Xiong; Fengjie Liu; Minwei Xie; Rong Chen; Qiao-Guo Tan (Environmental Pollution, 2025)

Thermal comfort and urban microclimate response: A new thermal environment assessment model for waterfront spaces in historic ancient towns - Yan Wang; Xinrui Liu; Rong Xie; Jiajing Wang; Qiwei Dong; Wanxiang Yao; Dahu Lin (Energy and Buildings, 2025)

Recent advancements in cation-intercalated vanadium oxide cathode materials for zinc-ion batteries - Kunxuan Li; Rong Li; Tiantian Guan; Lei Wang; Lingling Xie; Qing Han; Xuejing Qiu; Xiaoyu Cao; Limin Zhu (Chemical Engineering Journal, 2025)

Sodium bisulfite boosted exopolysaccharide production by Auxenochlorella protothecoides: Potential mechanisms harnessing H2O2 signaling and carbon reallocation - Rong Zhou; Wenli Zuo; Yuwei Xie; Yuting Wang; Chao Li; Yufang Tang; Zhenyao Wang; Yuqin Li (Bioresource Technology, 2025)

Wavelet kernel estimation of spatiotemporal models applied to ozone analysis in East China - Shuyue Wang; Xinjian Xie; Rong Ke (Environmental and Ecological Statistics, 2025)

Comammox and ammonia-oxidizing archaea dominated the nitrification under different nitrogen fertilizer levels in acid purple soil of Southwest China - Jun Xie; Jianguo Jiang; Jie Lu; Wencai Dai; Huarong Guo; Yuanxue Chen; Rong Huang; Zifang Wang; Ming Gao (Applied Soil Ecology, 2025)

Vision transformer based classification of sewer defects weighted loss model - Chunhou Ji; Zhiqiang Xie; Rong Li; Zhibing Yang; ZhiQun Hou (Tunnelling and Underground Space Technology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Mechanistic insights into efficient phosphorus adsorption and recovery from water using functional ZnO/ZnFe-LDHs alginate hydrogels - Shilong Cao; Xiangling Zhang; Shuqin Xie; Chen Wang; Jing Bai; Xuhao Li; Rong Zhang; Xinlu Xiao; Jiezhou Hu; Xiaoxia Jiang (Journal of Environmental Chemical Engineering, 2025)

Design, synthesis and antifungal activity of novel pyrazole-amide-isothiazole derivatives as succinate dehydrogenase inhibitors - Ai-ling Bao; Xian-song Xie; De-yuan Wang; Zi-quan Deng; Yun Chen; Dan Liu; Wei-yi Li; Xiao-rong Tang; Wei Cheng; Ying-kun Yan (Food Chemistry, 2025)

Smartphone-based dual-mode aptasensor with bifunctional metal-organic frameworks as signal probes for ochratoxin A detection - Yu-Long Li; Yan-Yue Chen; Fa-Ting Xie; Qiu-Xia Li; Tong Yang; Yun-Hui Yang; Rong Hu (Food Chemistry, 2025)

Inhibition of electron transfer in anaerobic ammonia-oxidized granular sludge by polyethylene terephthalate microplastics and nanoplastics: A new perspective on molecular docking and molecular dynamics simulations - Chaofan Xie; Dongyue Li; Jiarui Li; Linzhu Du; Yanshuo Wu; Rong Luo; Zheng Wang; Jun Li; Yuhan Zhu; Wei Guo (Chemical Engineering Journal, 2025)

PVA-enhanced green synthesis of CMC-based lithium adsorption films - Shengkai Liu; Huiling Li; Xi Li; Wei Wang; Chunguang Rong; Mengjie Yang; Yonggui Wang; Jing Wang; Yabei Xu; Daxin Liang; Yanjun Xie (Carbohydrate Polymers, 2025)

Performance prediction of urban tunnel purification system based on the verified random number screening algorithm - Jie Xia; Hao-Yi Zhao; Hui Ren; Long Chen; Fang Li; Wei-Rong Shi; Yi-Song Xie; Mei-Lan Tan; Fei Li; Bin Zhou (Sustainable Cities and Society, 2025)

Effects of stress factors on biogenic isoprene emissions and their contribution to ozone and secondary organic aerosols in China - Rong Song; Tijian Wang; Bingliang Zhuang; Mengmeng Li; Shu Li; Min Xie (Science of The Total Environment, 2025)

Long-term nitrogen application decreased mineral-associated organic carbon while increasing particulate organic carbon in purple soil in southwest China - Jun Xie; Yuanxue Chen; Rong Huang; Wencai Dai; Jie Lu; Zifang Wang; Ming Gao (Journal of Environmental Management, 2025)

Protecting anthocyanins of postharvest blueberries through konjac glucomannan/low-acyl gellan gum coatings contained thymol microcapsule during low-temperature storage - Jing Xie; Dur E. Sameen; Zhenkun Xiao; Huiyan Zhu; Yunya Lai; Tingting Tang; Xingyu Rong; Fengmei Fu; Wen Qin; Mingrui Chen; Yaowen Liu (Food Chemistry, 2025)

Dynamic estimation of the soil environmental carrying capacity for Benzo(a)pyrene in an industrial city, China: Insight from both duration and rate of regional emission - Xinyue Chen; Meie Wang; Tian Xie; Rong Jiang; Weiping Chen (Environmental Pollution, 2025)

Evaluating a novel portable semiconductor liquid cooling garment for reducing heat stress of healthcare workers in a hot-humid environment - Wenfang Song; Wenyue Lu; Sijing Yu; Rong Tang; Xinze Xie; Xuanxuan Zhou; Zihao Chen (Building and Environment, 2025)

Estimating the environmental Kuznets curve and its influencing factors of CO2 emissions: Insights from development stages and rebound effects - Rong Wu; Zihan Xie; Jieyu Wang; Shaojian Wang (Applied Geography, 2025)

Assessing Changes in China's Pond Water Quality From 1989 to 2020: Implications for Green Development in Aquaculture - Yuanshuai Duan; Lu Liu; Rong Tang; Shouqi Xie; Mingmei Yang; Zhimin Zhang; Dapeng Li (Reviews in Aquaculture, 2025)
Since 1989, China has become the world's largest aquaculture producer through pond culture, significantly contributing to global food security but potentially posing environmental threats. However, little is known about the changes in the pond water quality at broad spatial and temporal scales, thus creating challenges in the sustainability of pond aquaculture. Herein, we explore changes in water quality in China's aquaculture ponds from 1989 to 2020 and assess the waterbody's health status to optimize sustainable management strategies. This study highlights pond water quality changes closely associated with China's aquaculture practices, development, and related policies. Seasonal and regional farming variations significantly impact water quality, with peak aquaculture seasons and Central China and North China associated with the lowest water quality scores. Pond water quality initially declined with the rise of intensive aquaculture but improved after 2012 with the adoption of ecological engineering measures, eco‐farming practices, and policies supporting green development. Under a scenario combining these efforts, the water quality score in 2035 is projected to increase by 57% of the 2020 level. These findings reveal that national ecological initiatives and advancements in green aquaculture techniques and public policies can significantly enhance the water quality of China's aquaculture ponds, offering valuable insights into environmental governance in global agriculture.

Neutral purple soil acidification and mineralogical property changes due to long-term urea application in southwest China - Jun Xie; Dan Wang; Yuanxue Chen; Zhiqi Li; Wencai Dai; Rong Huang; Zifang Wang; Ming Gao (Soil and Tillage Research, 2024)

Biological nitrogen fixation in paddy soils is driven by multiple edaphic factors and available phosphorus is the greatest contributor - Tianlong HU; Yanhui ZHANG; Hui WANG; Haiyang JIN; Benjuan LIU; Zhibin LIN; Jing MA; Xiaojie WANG; Qi LIU; Hongtao LIU; Zhe CHEN; Rong ZHOU; et al. (Pedosphere, 2024)

Effect of zero-valent iron and magnetite on mitigating sulfate and lincomycin stress in anaerobic digestion: microbial succession and antibiotic resistant genes removal - Jing Xie; Jiaxin Zhu; Bolin Min; Rong He; Wenbiao Wang; Li Xie (Journal of Water Process Engineering, 2024)

A tumor-pH-responsive phthalocyanine as activatable type I photosensitizer for improved photodynamic immunotherapy - Ling Zhang; Rong-Bin Que; Ting-Ting Ke; Chao Wang; Wei Xie; Hong-Jie Sun; Bi-Yuan Zheng; Mei-Rong Ke; Jian-Dong Huang; Xingshu Li (Journal of Photochemistry and Photobiology B: Biology, 2024)

Epidemiological and genomic analysis revealed the significant role of flies in dissemination of carbapenem-resistant Enterobacteriaceae (CRE) in China - Hongwei Zhou; Hanyu Wang; Kaichao Chen; Miaomiao Xie; Zelin Yan; Yanyan Zhang; Yuchen Wu; Dejun Liu; Juan Wang; Ning Dong; Chang Cai; Yongning Wu; et al. (Journal of Hazardous Materials, 2024)

Migration mechanism of PTEs in polymetallic mines under pioneer phytoremediation: A Lanmuchang mercury-thallium mine perspective - Jichang Wen; Ruijia Yang; Xinlong Li; Rong Xie; Yonggui Wu (Environmental Research, 2024)

Identification and analysis of MAPK cascade gene families of Camellia oleifera and their roles in response to cold stress - Kaifeng Xing; Jian Zhang; Haoxing Xie; Lidong Zhang; Huaxuan Zhang; Liyun Feng; Jun Zhou; Yao Zhao; Jun Rong (Molecular Biology Reports, 2024)

The GaKAN2, a KANADI transcription factor, modulates stem trichomes in Gossypium arboreum - Xujiao Ren; Luying Yang; Yasir Muhammad; Yuxing Xie; Xinyi Lin; Li Yu; Yuefen Cao; Mingquan Ding; Yurong Jiang; Junkang Rong (Molecular Genetics and Genomics, 2024)

Co-culture of natural killer cells and tumor spheroids on a heterogeneous multilayer paper stack - Yuanyuan Xie; Xiaoyan Yang; Rong Pan; Lixia Gao; Ling Yu (Journal of Zhejiang University-SCIENCE B, 2024)

Assessment of carbon emissions and reduction potential in China's copper smelting industry - Rong Gao; Yao Shi; Chun Cao; Huiquan Li; Yuanbo Xie; Jingjing Shi; Chenmu Zhang; Xue Guan (Journal of Industrial Ecology, 2024)
As the largest producer and consumer of copper, China is facing enormous challenges from carbon peaking and neutrality. This article adopts “bottom‐up” and “top‐down” methods to construct a more accurate model, to predict the CO 2 emissions of China's copper smelting industry, and explores its potential for carbon reduction in the future from three scenarios as the baseline scenario (BAU), the general low‐carbon (NLC), and the enhanced low‐carbon (ELC). The results show that the CO 2 emissions can achieve a peak in 2028 either in NLC or ELC scenarios, with a peak range of 14.9–16.88 million tonnes. Prior to reaching the peak, the contributions of energy adjustment, material substitution, and process selection to carbon reduction have significantly improved, and the contribution rates increased from 30.91%, 4.11%, and 1.46% to 42.7%, 32.07%, and 15.63% in ELC scenario. After the peak, the contribution of energy adjustment gradually slows down, while the material substitution continues to increase, and the contribution rates increased from 21.25% and 32.07% to 29.38% and 40.01% in NLC and ELC scenarios. In the future, concentrate oxygen‐enriched bottom‐blowing smelting and direct refining from waste copper anode furnaces show ideal potential for carbon reduction before 2025, increasing the proportion of recycled copper production, and adjusting energy structure will be more effective from 2025 to 2035. The conclusions of this study can provide a scientific basis for formulating policy recommendations for green and low‐carbon development of the copper industry in China and all over the world in the future.

Azotosporobacter soli gen. nov., sp. nov., a novel nitrogen-fixing bacterium isolated from paddy soil - Cheng-Jie Xie; Ling Yao; Rong Tang; Shuang Han; Shang Yang; Hend Alwathnani; Christopher Rensing; Guo-Hong Liu; Shun-Gui Zhou (Antonie van Leeuwenhoek, 2024)

Two novel Fe(III)-reducing bacteria, Geothrix campi sp. nov. and Geothrix mesophila sp. nov., isolated from paddy soils - Shuang Han; Shang Yang; Rong Tang; Cheng-Jie Xie; Xing Liu; Guo-Hong Liu; Shun-Gui Zhou (Antonie van Leeuwenhoek, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Composted maize straw under fungi inoculation reduces soil N2O emissions and mitigates the microbial N limitation in a wheat upland - Rong Zhou; Hui Wang; Jingru Zhang; Zhe Chen; Penghui Jin; Tianlong Hu; Qing Bian; Xingwu Lin; Xueqiang Zhao; Zubin Xie (Science of The Total Environment, 2024)

Effects of 2,4,6-Trichloroanisole on the morphological development and motility of zebrafish - Yanxia Zuo; Fang Zhou; Rong Huang; Zhihui Jia; Juhong Xie; Guangxin Wang; Shuzhao Jia; Yongming Li; Manyi Wang; Lanjie Liao; Feng Ge; Yaping Wang (Science of The Total Environment, 2024)

Enhancing zinc-ion storage capacity of coal tar-derived porous carbon by functionalization and hierarchical structure design - Ruilun Xie; Guangming Rong; Ende Cao; Miaomiao Zhang; Xiangchun Liu; Zhao Lei; Tianyu Chen; Yujiao Tian (Fuel, 2024)

Synergistic adsorption and degradation of sulfonylurea herbicides by biochar-supported nano zero-valent iron composites in in-situ soil remediation - Wenwen Xie; Cheng Peng; Anqi Chen; Haoran Wang; Mabinty Sarah Tholley; Rong Qian; Sinan Lu; Wei Zhang; Xiuping Zhan (Chemical Engineering Journal, 2024)

Bioactives from biomass: Treasure for future potent antimicrobial applications - Weicheng Chen; Peng Zhang; Yucui Ding; Xiaobin Xie; Jianlong Fu; Rong Zhao; Yihan Xiao; Miodrag J. Lukic; Bin Li; Weishan Wang; Song Chen (Chemical Engineering Journal, 2024)

Epiphytic mosses alter Pinus massoniana deadwood microbial and physicochemical properties thereby influencing the decomposition process - Bingyang Shi; Xiurong Wang; Shuoyuan Yang; Hongmei Chen; Yang Zhao; Qiao Liu; Rong Zou; Muyan Xie; Lixin Duan; Fang Liao (Plant and Soil, 2024)

Gene expression profiles and metabolic pathways responsible for male sterility in cybrid pummelo - Rong Wang; Yang-Cao Shi; Bo Zhang; Wan-Rong Liu; Feng-Quan Tan; Fang Lu; Nan Jiang; Lai-Chao Cheng; Kai-Dong Xie; Xiao-Meng Wu; Wen-Wu Guo (Plant Cell Reports, 2024)

12-year continuous biochar application: Mitigating reactive nitrogen loss in paddy fields but without rice yield enhancement - Penghui Jin; Zhe Chen; Hui Wang; Runjin Lv; Tianlong Hu; Rong Zhou; Jingru Zhang; Xingwu Lin; Qi Liu; Zubin Xie (Agriculture, Ecosystems & Environment, 2024)

The concentration of dissolved organic matter impacts the neurobehavior in zebrafish larvae exposed to cyclophosphamide - Tianming Liu; Dongshen Shang; Weiqi Tian; Yindong Li; Rong Xie; Jianxing Zhao; Heru Dong (Environmental Science and Pollution Research, 2024)

County-level carbon budget and carbon compensation in the Yellow River Basin: a perspective with balancing efficiency and equity - Zhixiang Xie; Lu Wang; Rongqin Zhao; Liangang Xiao; Minglei Ding; Shuangsheng Yao; Xiaowei Chuai; Peijun Rong (Environment, Development and Sustainability, 2024)

Structurally diverse diterpenoids from the leaves of Croton mangelong and their anti-diabetic activity - Zhi-Yong Jiang; Qi Niu; Hao-Xin Wang; Hao-Nan Xu; Hong-Xi Xie; Lin Chen; Rong Chen; Hong-Lei Zhang; Lu Gao; Ai-Xue Zuo; Hong-Ping He (Phytochemistry, 2024)

Dicranopteris pedata improves soil quality by enhancing nutrient deposition, decreasing metal concentration, and boosting microbial diversity on abandoned rare earth elements mining sites - Xi-Wen Cui; Zhen-An Xu; Xian Chen; Zhi-Biao Chen; Jia-Bing Li; Rong-Rong Xie; Hong Zhang; Yong Zhang; Yong-He Han (Journal of Environmental Chemical Engineering, 2024)

Evaluation of the safety, immunogenicity and protective effect of an attenuated Pseudomonas plecoglossicida strain ΔgacS as the live vaccine for the large yellow croaker (Larimichthys crocea) - Tian-Jing Kang; Su-Ming Zhou; Xiao Xie; Rong-Rong Ma; Dong Qian; Shan Jin; Fei Yin (Fish & Shellfish Immunology, 2024)

Analysis of two-dimensional consolidation behavior of soils under cyclic loading considering exacerbated tunnel leakage - Sen-Lin Xie; An-Feng Hu; Zhi-Rong Xiao; Mei-Hui Wang; Xun-Jian Hu; Gabriele Della Vecchia; Stefano Mariani (Computers and Geotechnics, 2024)

Low oxygen adsorption energy barrier architectures to facilitate microenvironmental photocatalytic disinfection in Wei River - Lenan Yao; Yunyan Bai; Li Ding; Yayun Hu; Zuwang Zhang; Yajie Zhang; Rui Chen; Haijiao Xie; Jianlong Wang; Rong Wang (Chemical Engineering Journal, 2024)

Accelerated cartilage regeneration through immunomodulation and enhanced chondrogenesis by an extracellular matrix hydrogel encapsulating Kartogenin - Kai Huang; Qing-Yi Zhang; Jie Tan; Rong Nie; Zi-Yuan Feng; Yuan Liu; Ning Sheng; He-Xi Li; Yue-Qi Zhang; Bin Shen; Hui-Qi Xie (Chemical Engineering Journal, 2024)

The morphology of liquid CO2 hydrate films at different temperatures under saturation pressure - Yu-Jie Zhu; Yu Zhang; Yu-Zhou Chen; Yan Xie; Jin-Rong Zhong; Xiao-Hui Wang; Peng Xiao; Yi-Fei Sun; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2024)

Three-way junction-mediated three-letter coded SDA cascade CRISPR/Cas12a system for circRNA detection - Di Wu; Xin Liu; Lujia Tang; Baiying Li; Rong Zhao; Tong Feng; Xiangyang Xiao; Guoming Xie; Wenli Feng (Chemical Engineering Journal, 2024)

Injectable, antioxidative, and loaded with exosomes/Liproxstatin-1 hydrogel as a potential treatment for retinal ischemia–reperfusion by inhibiting ferroptosis and apoptosis - Mengling You; Rong Rong; Zhuotao Liang; Sijian Xie; Xiaoya Ma; Xiaobo Xia (Chemical Engineering Journal, 2024)

Effects of low-temperature stress on serum biochemical indicators, intestinal microbiome, and transcriptome of juvenile golden pompano (Trachinotus ovatus) - Rong-xin Li; Eric Amenyogbe; Yi Lu; Jing-hui Jin; Rui-tao Xie; Jian-sheng Huang (Aquaculture International, 2024)

Scalable thermochromic superhydrophobic collagen fiber-based wearable materials for all-weather self-adaptive radiative cooling and solar heating - Meng-Chen Huang; Chao-Hua Xue; Zhongxue Bai; Hui-Di Wang; Chao-Qun Ma; Yong-Gang Wu; Li Wan; Long Xie; Shi-Qiang Lv; Rong-Rong Gao; Wen-Min Zhang; Jun Cheng; et al. (Chemical Engineering Journal, 2024)

Superwetting MAX@SiO2 coatings with high photothermal conversion performances for efficient seawater desalination and anti-/de-icing - Helong Zhang; Chuxiong Qiu; Rong Zhang; Hao Zhang; Yunxia Chen; Tao Zeng; Fen Qiao; Lee Li; Ghafar Ali; Xiujian Zhao; Yi Xie (Chemical Engineering Journal, 2024)

Albumin tailoring molecular rotation and electrophilicity of a GSH-depleting radiosensitizer for potentiating ferroptosis-mediated radioimmunotherapy - Mingquan Gao; Xie Huang; Zifei Wu; Weidong Xiao; Zaizhi Du; Banghui Mo; Chuan Wu; Haiyan Xing; Weidong Wang; Rong Li; Shenglin Luo (Chemical Engineering Journal, 2024)

Remediation of Composite Contaminated Soil by Lead, Arsenic, Uranium and Thorium of Radioactive and Heavy Metal Using Chemical Drenching Combined with Passivation - Linxi Zhang; Jingwen Wang; Rong Zou; Dongxiang Xie; LiangLiang Chen; Honghai Wang; Kai Zeng; Ying Dai (Water, Air, & Soil Pollution, 2024)

Soil Organic Matter and Amorphous Oxides Determine the Surface Electrochemical Properties of Purple Soil Under Long-Term Inorganic and Organic Fertilization - Jun Xie; Rong Huang; Dongxun Wu; Wencai Dai; Zhengxin Deng; Yue Li; Xiaojun Shi; Yueqiang Zhang; Zifang Wang; Ming Gao (Journal of Soil Science and Plant Nutrition, 2024)

DOTAD: A Database of Therapeutic Antibody Developability - Wenzhen Li; Hongyan Lin; Ziru Huang; Shiyang Xie; Yuwei Zhou; Rong Gong; Qianhu Jiang; ChangCheng Xiang; Jian Huang (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Altered Function and Structure of the Cerebellum Associated with Gut–Brain Regulation in Crohn’s Disease: a Structural and Functional MRI Study - Yunfei Li; Yanling Zheng; Lan Rong; Yan Zhou; Zhen Zhu; Qian Xie; Zonghui Liang; Xiaohu Zhao (The Cerebellum, 2024)

The cytochrome P450 gene CYP4g1 driven by high temperature confers abamectin tolerance on Liriomyza trifolii through promoting cuticular hydrocarbons biosynthesis - Yu-Cheng Wang; Ya-Wen Chang; Hong-Fang Xie; Wei-Rong Gong; Cheng-Dong Wu; Yu-Zhou Du (Pesticide Biochemistry and Physiology, 2024)

Gas6-Axl signal promotes indoor VOCs exposure-induced pulmonary fibrosis via pulmonary microvascular endothelial cells–fibroblasts cross-talk - Qingping Liu; Yong Niu; Zijie Pei; Yizhe Yang; Yujia Xie; Mengruo Wang; Jingyuan Wang; Mengqi Wu; Jie Zheng; Peihao Yang; Haiyan Hao; Yaxian Pang; et al. (Journal of Hazardous Materials, 2024)

Co3O4–TiO2 supported into N-doped magnetic 3D porous microspheres as the “one stone with two birds” strategy for highly efficient removal of organic dyes via synergistic adsorption-photocatalysis - Xiaoyan Xie; Yingying Liu; Xi Deng; Mei Luo; Yude Liu; Rong Wang; Hailong Peng (Journal of Cleaner Production, 2024)

Effects of Premna microphylla turcz polysaccharide on rheological, gelling, and structural properties of mung bean starch and their interactions - Weiqi Fei; Liyuan Rong; Xin Qi; Xianxiang Chen; Yi Luo; Huiliang Wen; Jianhua Xie (Food Research International, 2024)

Pyrolysis-free coupling strategy to synthesize two-dimensional oxygen reaction electrocatalysts for rechargeable Zn-air batteries - Peng-Fei Xie; Hao Hu; Lingzhe Fang; Xiaohua Yu; Ju Rong; Xiaoyi Qiu; Feng Wu; Tao Li; Minhua Shao; Jin-Cheng Li (Chemical Engineering Journal, 2024)

Relationship between photochromism and persistent luminescence in barium-magnesium silicates - Rujun Yang; Long Chen; Cunjian Lin; Honghui Huang; Zishuang Wu; Chenhan Zhan; Yixi Zhuang; Rong-Jun Xie (Chemical Engineering Journal, 2024)

Adenylate kinase phosphate energy shuttle underlies energetic communication in flagellar axonemes - Huan Wu; Yanman Zhang; Yuqian Li; Shuya Sun; Jintao Zhang; Qingsong Xie; Yue Dong; Shushu Zhou; Xuan Sha; Kuokuo Li; Jinyi Chen; Xin Zhang; et al. (Science China Life Sciences, 2024)

The protective effect and mechanism of piperazine ferulate in rats with 5/6 nephrectomy-caused chronic kidney disease - Xiu-Meng Zhang; Xin-Ran Min; Dan Li; Bo Li; Yi-Xin rui; Hong-Xiao Xie; Rong Liu; Nan Zeng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Collective effects of rising average temperatures and heat events on oviparous embryos - Liang Ma; Dan‐Yang Wu; Yang Wang; Joshua M. Hall; Chun‐Rong Mi; Hong‐Xin Xie; Wei‐Jie Tao; Chao Hou; Kun‐Ming Cheng; Yong‐Pu Zhang; Ji‐Chao Wang; Hong‐Liang Lu; et al. (Conservation Biology, 2024)
Survival of the immobile embryo in response to rising temperature is important to determine a species’ vulnerability to climate change. However, the collective effects of 2 key thermal characteristics associated with climate change (i.e., rising average temperature and acute heat events) on embryonic survival remain largely unexplored. We used empirical measurements and niche modeling to investigate how chronic and acute heat stress independently and collectively influence the embryonic survival of lizards across latitudes. We collected and bred lizards from 5 latitudes and incubated their eggs across a range of temperatures to quantify population‐specific responses to chronic and acute heat stress. Using an embryonic development model parameterized with measured embryonic heat tolerances, we further identified a collective impact of embryonic chronic and acute heat tolerances on embryonic survival. We also incorporated embryonic chronic and acute heat tolerance in hybrid species distribution models to determine species’ range shifts under climate change. Embryos’ tolerance of chronic heat (T‐chronic) remained consistent across latitudes, whereas their tolerance of acute heat (T‐acute) was higher at high latitudes than at low latitudes. Tolerance of acute heat exerted a more pronounced influence than tolerance of chronic heat. In species distribution models, climate change led to the most significant habitat loss for each population and species in its low‐latitude distribution. Consequently, habitat for populations across all latitudes will shift toward high latitudes. Our study also highlights the importance of considering embryonic survival under chronic and acute heat stresses to predict species’ vulnerability to climate change.

“Edge in-situ heterogeneous” BiOI based on defect engineering and non-noble metal deposition: Boosting visible-light photocatalytic sterilization - Bangfeng Fu; Yifan Pan; Peng Zhao; Liang Zhang; Junchen Zhuo; Jianxing Feng; Bingzhi Li; Lenan Yao; Jiafeng Xi; Xi Lan; Linpin Luo; Ting Du; et al. (Chemical Engineering Journal, 2024)

A Novel Method for Analyzing Sandbar Distribution in Shelf-Type Tidal Deltas Using Sediment Dynamic Simulation - Mingming Tang; Sichen Xiong; Qian Zhang; Ruifeng Hong; Chenyang Peng; Rong Xie (Journal of Marine Science and Engineering, 2024)
Shallow marine shelf sedimentation is a hot and difficult topic in today’s reservoir sedimentology research, and it is widely present in the world. The shallow marine shelf sedimentation is not only affected by complex hydrodynamic effects such as tides and waves, but also controlled by bottom tectonic features, forming a complex and varied sedimentation pattern. During the Middle Jurassic period, the northern part of West Siberian Basin was characterized by a shallow marine shelf sedimentary environment. In the central reion of this basin, a typical tectonic uplift zone developed, forming a tectonic background of “one uplift zone between two depressions”. Simultaneously, the dominant influence of tides in the shallow marine shelf environment facilitated the formation of a typical shelf-type tidal delta sedimentation system in the Jurassic strata of the northern part of West Siberian Basin. This sedimentation constitutes a significant natural gas reservoir, and it is important to investigate the sedimentary evolution of shelf-type tidal deltas and to clarify the internal structure and distribution of sedimentary sand bodies and interlayers in shelf-type tidal deltas, which is the basis for the fine development of this type of reservoir. This paper takes the Jurassic strata in the Y region of northern part of West Siberian Basin as the research object, and conducts numerical simulation based on sedimentary dynamics for the shelf-type tidal delta sedimentation formed under the tectonic background of “one uplift zone between two depressions”. In addition, tidal amplitude and initial water level were selected for different hydrodynamic factors to study the main controlling factors of shelf-type tidal delta sedimentation. The simulation results show that tidal amplitude is positively correlated with three-dimensional configuration characteristic parameters of the sedimentary sand bodies, and the development of tidal bars becomes more and more limited as the initial water level increases. This paper systematically investigates the sedimentary evolution of shelf-type tidal delta under the tectonic background of “one uplift zone between two depressions” by the sedimentary dynamics method, which deepens the understanding of the shelf-type tidal delta sedimentation process and provides a new thinking for the development of this sedimentary reservoir type (School of Geosciences China University of Petroleum (East China)).

Formation potential of disinfection byproducts during chlorination of petroleum hydrocarbon-contaminated drinking water - Mandy-Tanita Brinkmann; Kexin Rong; Yuefeng Xie; Tao Yan (Chemosphere, 2024)

Path tracking control for brake-steering tracked vehicles based on an improved pure pursuit algorithm - Chenming Hu; Yu Ru; Xianzhe Li; Shuping Fang; Hongping Zhou; Xianghai Yan; Mengnan Liu; Rong Xie (Biosystems Engineering, 2024)

Extraction, structural characterization, and antioxidant activity of polysaccharides from three microalgae - Yang Zhao; Chun Han; Yangyingdong Wu; Qianchen Sun; Meng Ma; Zhen Xie; Rong Sun; Haiyan Pei (Science of The Total Environment, 2024)

Two-step synthesis of coconut shell biochar-based ternary composite to efficiently remove organic pollutants by photocatalytic degradation - Shipeng Zhang; Rong Wang; Jinhua Zhu; Xiaoyan Xie; Mei Luo; Hailong Peng; Yude Liu; Fei Feng; Ronghui Shi; Wang Yin (Journal of Environmental Chemical Engineering, 2024)

Preparation and characterization of industrial solid waste based geopolymer for immobilizing Pb and Cd in the sediment - Hao Rong; Hongzhong Xie; Teng Wang (Journal of Environmental Chemical Engineering, 2024)

Biomineralization-inspired porous calcium carbonate microspheres as a controlled release system of herbicides/pesticides - Yaoxun Zeng; Xinyi Li; Fangzheng Chen; Huiling Ye; Keyi Rong; Zhili Ran; Binhong Liu; Zhenxing Pan; Xiuxian Xie; Junze Tang; Xujie Liu; Yan He (Journal of Environmental Chemical Engineering, 2024)

Human milk oligosaccharide 2′-fucosyllactose alleviates DSS-induced ulcerative colitis via improving intestinal barrier function and regulating gut microbiota - Xianxiang Chen; Jiaruo Hu; Jun Yang; Qiang Yu; Yi Chen; Mingyue Shen; Liyuan Rong; Jianhua Xie (Food Bioscience, 2024)

Effects of rice bran stabilization procedures and proteases on rice bran protein hydrolysates - Kefan Ouyang; Qin Tao; Hexiang Xie; Qing Guo; Liu Rong; Fangjie Xiao; Hua Xiong; Qiang Zhao (Food Bioscience, 2024)

Polyoxovanadate Li7[V15O36(CO3)] and its derivative γ-LiV2O5 as superior performance cathode materials for aqueous zinc-ion batteries - Haoran Xiao; Xin Du; Rong Li; Hao Jin; Lingling Xie; Qing Han; Xuejing Qiu; Xinli Yang; Limin Zhu; Xiaoyu Cao (Chemical Engineering Journal, 2024)

Chemical constituents of the deep-sea-derived fungus Trichoderma simmonsii ZEN3 and their chemotaxonomic significance - Li-Fang Liu; Yuan Wang; Rong Chao; Lin Xu; Zheng-Biao Zou; Kai Zhang; Ming-Min Xie; Xian-Qiang Chen; Cheng-Hai Gao; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Chemical constituents and chemotaxonomic research of the deep-sea-derived fungus Aspergillus japonicus W6 - Tong Yu; Rong Chao; Zheng-Biao Zou; Jia-Xin Duan; Kai Zhang; You Li; Ming-Min Xie; Yong Zhang; Ying-Ni Pan; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Fibroblast-localized lncRNA CFIRL promotes cardiac fibrosis and dysfunction in dilated cardiomyopathy - Shuai Yuan; Xudong Zhang; Jiabing Zhan; Rong Xie; Jiahui Fan; Beibei Dai; Yanru Zhao; Zhongwei Yin; Qian Liu; Dao Wen Wang; Huaping Li; Chen Chen (Science China Life Sciences, 2024)

Analysis of mild and severe neonatal enterovirus infections in a Chinese neonatal tertiary center: a retrospective case-control study - Junshuai Li; Jingjing Xie; Min Zhang; Zhuojun Xiao; Fan Zhang; Weiqing Huang; Yong Zhou; Weiqun Yan; Rong Zhang; Xiaoming Peng (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Histopathological analysis of the wall enhancement of the spinal dural arteriovenous fistulae’s draining veins - Xiaojun Hu; Yuhang Diao; Zhenghao Hao; Mingyu Hao; Minghao Xie; Hongtao Rong; Tao Zhu (Acta Neurologica Belgica, 2024)

Spartina alterniflora invasion altered phosphorus retention and microbial phosphate solubilization of the Minjiang estuary wetland in southeastern China - Yan-Zhen Lin; Qi-Qi Chen; Yi-Fan Qiu; Rong-Rong Xie; Hong Zhang; Yong Zhang; Jia-Bing Li; Yong-He Han (Journal of Environmental Management, 2024)

Soil inorganic carbon stock and its changes across the Tibetan Plateau during the 1980s–2020s - Honghong Lin; Xingwu Duan; Yifan Dong; Ronghua Zhong; Hua Zheng; Yun Xie; Li Rong; Haijuan Zhao; Shengzhao Wei (Global and Planetary Change, 2024)

Space-specific flux estimation of atmospheric chemicals from point sources to soil - Xinyue Chen; Meie Wang; Tian Xie; Rong Jiang; Weiping Chen (Environmental Pollution, 2024)

Building a stable and robust anti-interference DNA dissipation system by eliminating the accumulation of systemic specified errors - Luojia Wang; Wang Luo; Zhi Weng; Zhongzhong Wang; You Wu; Rong Zhao; Xiaole Han; Xin Liu; Jianhong Zhang; Yujun Yang; Guoming Xie (Analytica Chimica Acta, 2024)

Metabolomics provides insights into the alleviating effect of dietary Caulerpa lentillifera on diquat-induced oxidative damage in zebrafish (Danio rerio) liver - Xiang Lin; Zhongqun Liu; Ye Xiao; Xiaocen Xie; Yongqiang Wang; Haiping Li; Rong Wang; Xi Xie; Yingxia Zhang; Yanting Song; Wenting Hu (Aquaculture, 2024)

Excessive fluoride induces ovarian function impairment by regulating levels of ferroptosis in fluorosis women and ovarian granulosa cells - Nan Geng; Siyuan Dong; Pengpeng Xie; Yi Zhang; Rong Shi; Chen Chen; Zhao Xu; Qun Chen (Reproductive Toxicology, 2024)

Enhancement of hydrogenotrophic methanogenesis for methane production by nano zero-valent iron in soils - Weijie Peng; Jinrong Lu; Jiajie Kuang; Rong Tang; Fengyi Guan; Kunting Xie; Lihua Zhou; Yong Yuan (Environmental Research, 2024)

The concentration of dissolved organic matter impacts the neurobehavior in female zebrafish exposed to cyclophosphamide - Tianming Liu; Heru Dong; Jianxing Zhao; Dongshen Shang; Yindong Li; Rong Xie (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Influencing assessment of mask wearing on thermal comfort and pleasure during outdoor walking in hot summer region - Rong Hu; Jianlin Liu; Yongxin Xie; Yun Su; Zhaosong Fang; Yongfa Diao; Henggen Shen (Urban Climate, 2024)

Recovery and genetic characterization of clinically-relevant ST2 carbapenem-resistant Acinetobacter baumannii isolates from untreated hospital sewage in Zhejiang Province, China - Danxia Gu; Yuchen Wu; Kaichao Chen; Yanyan Zhang; Xiaoyang Ju; Zelin Yan; Miaomiao Xie; Edward Wai Chi Chan; Sheng Chen; Zhi Ruan; Rong Zhang; Jun Zhang (Science of The Total Environment, 2024)

Underlying the inhibition mechanisms of sulfate and lincomycin on long-term anaerobic digestion: Microbial response and antibiotic resistance genes distribution - Li Xie; Jiaxin Zhu; Jing Xie; Jun Xu; Rong He; Wenbiao Wang (Science of The Total Environment, 2024)

Cypermethrin induces Sertoli cell apoptosis through endoplasmic reticulum-mitochondrial coupling involving IP3R1-GRP75-VDAC1 - Rui Zhang; Xu-Xu Wang; Jia-fei Xie; Ting-ting Yao; Qian-wen Guo; Qi Wang; Zhen Ding; Jin-Peng Zhang; Mei-Rong Zhang; Li-Chun Xu (Reproductive Toxicology, 2024)

Rapid colorimetric and fluorescence identification of Pinelliae Rhizoma and adulterate Rhizoma Typhonii Flagelliformis using direct-LAMP assay - Huilin Li; Jiaqi Cui; Hongling Chen; Hongying Li; Yuchen Xie; Wenjun Song; Rong Chen (Food Chemistry, 2024)

Biodiversity and core microbiota of key-stone ecological clusters regulate compost maturity during cow-dung-driven composting - Xin Liu; Xiangmin Rong; Pan Jiang; Junyan Yang; Han Li; Yong Yang; Xingxiang Deng; Guixian Xie; Gongwen Luo (Environmental Research, 2024)

TiO2-x modified Ni/SBA-15 catalysts for dibenzofuran hydrodeoxygenation - Yu-Kun Wang; Hao-Wei Li; Yu-Rong Liu; Zi-Zheng Xie; Zhen-Yi Du; Xing-Bao Wang; Wen-Ying Li (Chemical Engineering Journal, 2024)

Comprehensive plasmid toolkit for multipart assembly in the Dunaliella salina nuclear system - Hao-Hong Chen; Yu-Chen Xie; Shan-rong Xie; Jian-Guo Jiang (Algal Research, 2024)

Comparative study on anthropogenic impacts on soil PAHs: Accumulation and source apportionment in tourist and industrial cities in Hebei Province, China - Tian Xie; Meie Wang; Rong Jiang; Lei Li; Xinyue Chen; Suriyanarayanan Sarvajayakesavalu; Weiping Chen (Science of The Total Environment, 2024)

Synergistic dual-regulating the electronic structure of NiMo selenides composite for highly efficient hydrogen evolution reaction - Rong Li; Song Xie; Yujie Zeng; Qiangqiang Zhao; Minqin Mao; Zhitian Liu; Paul K. Chu; Xiang Peng (Fuel, 2024)

Effect of gellan gum on the rheology, gelling, and structural properties of thermally induced pea protein isolate gel - Yulin Li; Xin Qi; Liyuan Rong; Jinwang Li; Mingyue Shen; Jianhua Xie (Food Hydrocolloids, 2024)

Rational construction of MOF-on-MOF heterojunction with an array of flexible two-dimensional microsheets for efficient CO2 photoreduction - Bing He; Ying-Jie Wang; Xuefeng Bai; He Bian; Yabo Xie; Rui Li; Jian-Rong Li (Chemical Engineering Journal, 2024)

Molecular dynamics simulation and experimental analysis of nucleation and growth mechanism of mixed inorganic salts in supercritical water - Siqi Rong; Ruoyu Wang; Anlan Xie; Zhiyong Peng; Peng Cao; Mingyi Zhang; Jinhua Cui; Yunan Chen; Liejin Guo (Chemical Engineering Journal, 2024)

Influence analysis of network evolution on Parrondo effect - Ye Ye; Zhuo-yuan Zhai; Xiao-Rong Hang; Neng-gang Xie (BioSystems, 2024)

In situ biomass burning enhanced the contribution of biogenic sources to sulfate aerosol in subtropical cities - Tingting Li; Jun Li; Luhua Xie; Boji Lin; Hongxing Jiang; Rong Sun; Xiao Wang; Ben Liu; Chongguo Tian; Qilu Li; Wanglu Jia; Gan Zhang; et al. (Science of The Total Environment, 2024)

Exposure levels and determinants of placental polybrominated diphenyl ethers in Chinese pregnant women - Yijun Liu; Yan Xie; Yingkuan Tian; Juan Liao; Derong Fang; Linglu Wang; Rong Zeng; Shimin Xiong; Xingyan Liu; Qing Chen; Ya Zhang; Hongyu Yuan; et al. (Environmental Research, 2024)

A pleiotropic SIS-based hydrogel with immunomodulation via NLRP3 inflammasome inhibition for diabetic bone regeneration - Ning Sheng; Fei Xing; Qing-Yi Zhang; Jie Tan; Rong Nie; Kai Huang; He-Xi Li; Yan-Lin Jiang; Bo Tan; Zhou Xiang; Hui-Qi Xie (Chemical Engineering Journal, 2024)

Zn(II) Coordination Polymer: Luminescence Sensing for Fe3+ Ion and Used as Metal Gel Particles Against Lung Cancer - Wen Dong; Rong Xie; Nan Yang; Shengming Liu (Journal of Fluorescence, 2023)

Mystery of bisphenol F-induced nonalcoholic fatty liver disease-like changes: Roles of Drp1-mediated abnormal mitochondrial fission in lipid droplet deposition - Linwei Zhang; Xuexue Xie; Jingxian Tao; Sizhe Wang; Miaoyang Hu; Xi Wang; Zheng Yu; Liuting Xu; Yuxin Lin; Weilan Wu; Jie Cheng; Linlin Wu; et al. (Science of The Total Environment, 2023)

Pedotransfer functions for predicting bulk density of coastal soils in East China - Guanghui ZHENG; Caixia JIAO; Xianli XIE; Xuefeng CUI; Gang SHANG; Chengyi ZHAO; Rong ZENG (Pedosphere, 2023)

High light and temperature enhancing astaxanthin production in Microcystis aeruginosa—Providing a potential thought for controlling cyanobacterial blooms through resource utilization - Lexin Huang; Rong Hu; Yike Xie; Xiaonan Zhou; Tiefeng Zheng; Tianyu Huang; Zhaojiang Zuo (Journal of Water Process Engineering, 2023)

Selective galena depression mechanism of tea polyphenol in chalcopyrite flotation - Haiyang He; Jianjun Fang; Zhilian Qiu; Dianwen Liu; Haiyun Xie; Peilun Shen; Rong Peng; Liguo Peng; Shuang Qin; Shiqin Dong (Minerals Engineering, 2023)

Multifunctional dumbbell probes-based logic circuits: microRNAs logic detection and tumor cells identification - Xin Liu; Baiying Li; Qian Liu; Li Zhang; Rong Zhao; Di Wu; Luojia Wang; Zhongzhong Wang; Guoming Xie; Wenli Feng (Analytica Chimica Acta, 2023)

Positive relationships between species diversity and genetic diversity on a local scale at Mt. Wu Yi, China - Lei Xie; YueYao Feng; Rong Zhao; Ting Lv; NingJie Wang; Yao Li; Xiao Zheng; ShuiFei Chen; Hui Ding; YanMing Fang (Biodiversity and Conservation, 2023)

G-quadruplex based biosensors for the detection of food contaminants - Rong Du; Xiebingqing Yang; Ping Jin; Yahui Guo; Yuliang Cheng; Hang Yu; Yunfei Xie; He Qian; Weirong Yao (Critical Reviews in Food Science and Nutrition, 2023)

Evaluation of the toxicity of clozapine on the freshwater diatom Navicula sp. using the FTIR spectroscopy - Hao-Jun Lei; Xin-Rong Wei; Li-Xia Li; Wei-Jun Sun; Hong-Xing Chen; Dan Li; Lingtian Xie (Chemosphere, 2023)

Selective extraction of Au(III) and Pd(II) using p-tert-butyl-thiacalix[4]arene tetrathioamide as extractant - Shuaiyuan Ning; Rong Xie; Lelin Zeng; Kewen Tang (Process Safety and Environmental Protection, 2023)

Tigliane diterpenoids with cytotoxic activities from Croton damayeshu - Rong-Lin Jia; Qian Liang; Jia-Xin Hu; Si-Da Xie; Xiao-Min Su; Wen-Hui Xu (Phytochemistry Letters, 2023)

Ontology-Based BERT Model for Automated Information Extraction from Geological Hazard Reports - Kai Ma; Miao Tian; Yongjian Tan; Qinjun Qiu; Zhong Xie; Rong Huang (Journal of Earth Science, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Solvent-freely polymerizing catechol and paraformaldehyde to nitrogen-rich carbon for high-volumetric-performance supercapacitor - Yushuai Yao; Rong Zhou; Yi Yu; Jian Chen; Cheng Du; Yan Zhang; Tao Long; Liu Wan; Qiuyue Wang; Mingjiang Xie (Chemical Engineering Journal, 2023)

Electrospun polyvinyl alcohol-chitosan dressing stimulates infected diabetic wound healing with combined reactive oxygen species scavenging and antibacterial abilities - Haibing Liu; Rong Chen; Pinkai Wang; Jinlang Fu; Zinan Tang; Jiajun Xie; Yanhong Ning; Jian Gao; Qiang Zhong; Xin Pan; Ding Wang; Mingyuan Lei; et al. (Carbohydrate Polymers, 2023)

Biochar application increases biological nitrogen fixation in soybean with improved soil properties in an Ultisol - Xingwu Lin; Zubin Xie; Tianlong Hu; Hui Wang; Zhe Chen; Rong Zhou; Penghui Jin (Journal of Soil Science and Plant Nutrition, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Detection of spatiotemporal changes in ecological quality in the Chinese mainland: Trends and attributes - Yang Li; Haifeng Tian; Jingfei Zhang; Siqi Lu; Zhixiang Xie; Wei Shen; Zhicheng Zheng; Mengdi Li; Peijun Rong; Yaochen Qin (Science of The Total Environment, 2023)

Preparation and characterization of curcumin-loaded debranched starch/Mesona chinensis polysaccharide microcapsules: Loading levels and in vitro release - Wenhao Xiao; Mingyue Shen; Jinwang Li; Yulin Li; Xin Qi; Liyuan Rong; Wenmeng Liu; Jianhua Xie (Food Hydrocolloids, 2023)

Automatic Alberta Stroke Program Early Computed Tomographic Scoring in patients with acute ischemic stroke using diffusion-weighted imaging - Yan Wu; Rong Sun; Yuanzhong Xie; Shengdong Nie (Medical & Biological Engineering & Computing, 2023)

TFEB: a double-edged sword for tumor metastasis - Jun-Hu Hu; Shou-Ye Li; Li-Hua Yu; Zhen-Rong Guan; Ya-Ping Jiang; Die Hu; Hao-Jie Wang; Li-Ping Zhao; Zhao-Huang Zhou; Ya-Xin Yan; Tian Xie; Zhi-Hui Huang; et al. (Journal of Molecular Medicine, 2023)

Thymic tuft cells: potential “regulators” of non-mucosal tissue development and immune response - Jun Sun; Ming-xin Li; Yi-meng Xie; Ya-ru Zhang; Yu-rong Chai (Immunologic Research, 2023)

Interspecies calibration for biomonitoring metal contamination in coastal waters using oysters and mussels - Xue Cao; Guangbin Zhong; Ke Pan; Jing Qian; Minwei Xie; Rong Chen; Yongyan Liao; Qiao-Guo Tan (Science of The Total Environment, 2023)

A hierarchical In2O3@ZIF-67 architecture with upgraded CO2 photoreduction performances - Ying-Jie Wang; Bing He; Dejun Ma; Rui Li; Yabo Xie; Jian-Rong Li (Chemical Engineering Journal, 2023)

Profit versus Sustainability in Bikeshare - Huiyi Litan; Ke Rong; Youran Wu; Danxia Xie; Hanzhe Zhang; Dong Zhao (Sustainable Cities and Society, 2023)

SRSF1 is crucial for male meiosis through alternative splicing during homologous pairing and synapsis in mice - Longjie Sun; Juan Chen; Rong Ye; Zheng Lv; Xuexue Chen; Xiaomei Xie; Yuheng Li; Chaofan Wang; Pengbo Lv; Lu Yan; Shuang Tian; Xiaohong Yao; et al. (Science Bulletin, 2023)

BPA exposure enhances the metastatic aggression of ovarian cancer through the ERα/AKT/mTOR/HIF-1α signaling axis - Xin Xie; Yan Zhu; Huimin Cheng; Haili Li; Yadi Zhang; Rong Wang; Wenyong Li; Fengrui Wu (Food and Chemical Toxicology, 2023)

Sulfurospirillum oryzae sp. nov., A Novel Nitrogen-Fixing Bacterium Isolated from Paddy Soil - Cheng-Jie Xie; Shang Yang; Rong Tang; Shuang Han; Guo-Hong Liu; Shun-Gui Zhou (Current Microbiology, 2023)

The capacity of land carbon sinks in poverty-stricken areas in China continues to increase in the process of eradicating extreme poverty: evidence from a study of poverty-stricken counties on the Qinghai-Tibet Plateau - Lei Hua; Rong Ran; Mingjuan Xie; Tingrou Li (Environment, Development and Sustainability, 2023)

A data driven method for multi-step prediction of ship roll motion in high sea states - Dan Zhang; Xi Zhou; Zi-Hao Wang; Yan Peng; Shao-Rong Xie (Ocean Engineering, 2023)

Identification of Heterophilic Epitopes of H1N1 Influenza Virus Hemagglutinin - Jing-ying Sun; Chun-yan Guo; Guo-rong Wang; Li-ting Yan; Qing Feng; Yan Li; Xue-ping Huo; Xin Xie; Jun Hu; Li-jun Sun (Current Microbiology, 2023)

A systematic analysis and evaluation of nutritional composition of 23 strains of marine microalgae commonly used in aquaculture - Jia-Xing Zhang; Zhao-Shou Ran; Hai-Xuan Xie; Fei Kong; Meng-Qi Zhang; Yao Zhou; Yan-Rong Li; Kai Liao; Xiao-Jun Yan; Ji-Lin Xu (Algal Research, 2023)

Orange protein (DbOR) from the salt-tolerant green alga Dunaliella bardawil mediates photosynthesis against heat stress via interacting with DbPsbP1 - Ming-Hua Liang; Jv-Liang Dai; Shan-Rong Xie; Jing-Xuan Wu; Hao-Hong Chen; Jian-Guo Jiang (Algal Research, 2023)

Geothrix oryzisoli sp. nov., a ferric iron-reducing bacterium isolated from paddy soil - Shuang Han; Rong Tang; Shang Yang; Cheng-Jie Xie; Manik Prabhu Narsing Rao; Christopher Rensing; Guo-Hong Liu; Shun-Gui Zhou (Antonie van Leeuwenhoek, 2023)

The application of 3D printing technology on starch-based product: A review - Liyuan Rong; Xianxiang Chen; Mingyue Shen; Jun Yang; Xin Qi; Yulin Li; Jianhua Xie (Trends in Food Science & Technology, 2023)

The constancy of chemical weathering intensity on hillslopes in the arid to semiarid Qilian Mountains, NE Tibetan Plateau - Haopeng Geng; Jian Zhang; Rong Xie; Songbo Dai; Baotian Pan (Science of The Total Environment, 2023)

Insight into the effects and mechanism of cellulose and hemicellulose on anaerobic digestion in a CSTR-AnMBR system during swine wastewater treatment - Yuzheng Wang; Yuqi Chen; Hongyu Xie; Wenzhi Cao; Rong Chen; Zhe Kong; Yanlong Zhang (Science of The Total Environment, 2023)

Social environments still matter: The role of physical and social environments in place attachment in a transitional city, Guangzhou, China - Jiang Chang; Zihan Lin; Igor Vojnovic; Jiaguo Qi; Rong Wu; Dixiang Xie (Landscape and Urban Planning, 2023)

Enhancement of acidic sites in layered MnO2 for the highly efficient selective catalytic oxidation of gaseous ammonia - Yu Zhou; Shaopeng Rong; Huifang Xie; Yanfang Feng; Danni Ding; Weijiang He; Nan Zhang; Jingling Lu (Journal of Environmental Chemical Engineering, 2023)

Fibrillation modification to improve the viscosity, emulsifying, and foaming properties of rice protein - Xin Qi; Yulin Li; Jinwang Li; Liyuan Rong; Wentao Pan; Mingyue Shen; Jianhua Xie (Food Research International, 2023)

Purple red rice bran anthocyanins reduce the digestibility of rice starch by forming V-type inclusion complexes - Weidong Zhang; Haibin Zhu; Liyuan Rong; Yi Chen; Qiang Yu; Mingyue Shen; Jianhua Xie (Food Research International, 2023)

Adsorption of heavy metals on biodegradable and conventional microplastics in the Pearl River Estuary, China - Min Shi; Qun Xie; Zhen-Liang Li; Yun-Feng Pan; Zhen Yuan; Lang Lin; Xiang-Rong Xu; Heng-Xiang Li (Environmental Pollution, 2023)

Polyphenolic-modified cellulose acetate membrane for bone regeneration through immunomodulation - Qing-Yi Zhang; Jie Tan; Kai Huang; Rong Nie; Zi-Yuan Feng; Chen-Yu Zou; Qian-Jin Li; Jun Chen; Ning Sheng; Bo-Quan Qin; Zhi-Peng Gu; Li-Min Liu; et al. (Carbohydrate Polymers, 2023)

The mutual interactions among ozone, fine particulate matter, and carbon dioxide on summer monsoon climate in East Asia - Danyang Ma; Tijian Wang; Beiyao Xu; Rong Song; Libo Gao; Huimin Chen; Xuejuan Ren; Shu Li; Bingliang Zhuang; Mengmeng Li; Min Xie; Eri Saikawa (Atmospheric Environment, 2023)

Episodic magmatism in the Dananhu arc, eastern Tianshan: Implications for the Late Palaeozoic tectonic evolution of the North Tianshan Ocean - Rong-Song Tian; M.N. Muhtar; Guo-Ai Xie; Chang-Zhi Wu (International Geology Review, 2023)

The effectiveness of eight-years phosphorus reducing inputs on double cropping paddy: Insights into productivity and soil-plant phosphorus trade-off - Ning Su; Guixian Xie; Zhiwei Mao; Qiaorong Li; Tian Chang; Yuping Zhang; Jianwei Peng; Xiangmin Rong; Gongwen Luo (Science of The Total Environment, 2023)

Preparation of red mud-based zero-valent iron materials by biomass pyrolysis reduction: Reduction mechanism and application study - Xie Liu; Rong Rong; Min Dai; Hengzhi Bian; Changsheng Peng (Science of The Total Environment, 2023)

Site-specific ecological effect assessment at community level for polymetallic contaminated soil - Rong Jiang; Meie Wang; Tian Xie; Weiping Chen (Journal of Hazardous Materials, 2023)

Aroma formation and transformation during sealed yellowing process of Pingyang yellow tea - Rong-Jian Dong; Xie-Huang Sheng; Qian-Tu Xie; Xiaolin Huang; Fujie Yan; Songbai Liu (Food Research International, 2023)

Effects of long-term grazing exclusion on vegetation structure, soil water holding capacity, carbon and nitrogen sequestration capacity in an alpine meadow on the Tibetan Plateau - Yong-sheng Yang; Fa-wei Zhang; Xian-rong Xie; Jun-bang Wang; Ying-nian Li; Xiao-tao Huang; Hui-ting Li; Hua-kun Zhou (Journal of Mountain Science, 2023)

A novel sulfate-reducing and nitrogen-fixing bacterium Fundidesulfovibrio soli sp. nov., isolated from paddy soils - Shang Yang; Rong Tang; Cheng-Jie Xie; Shuang Han; Christopher Rensing; Guo-Hong Liu; Shun-Gui Zhou (Archives of Microbiology, 2023)

Risk assessment and environmental determinants of urinary phthalate metabolites in pregnant women in Southwest China - Nian Wu; Lin Tao; Kunming Tian; Xia Wang; Caidie He; Songlin An; Yingkuan Tian; Xiang Liu; Wei Chen; Haonan Zhang; Pei Xu; Dengqing Liao; et al. (Environmental Science and Pollution Research, 2023)

Effects of low-temperature stress on intestinal structure, enzyme activities and metabolomic analysis of juvenile golden pompano (Trachinotus ovatus) - Rong-xin Li; Eric Amenyogbe; Yi Lu; Jing-hui Jin; Rui-tao Xie; Jian-sheng Huang (Frontiers in Marine Science, 2023)
Water temperature plays a crucial role in the growth, survival, and reproduction of fish species, as they make up the majority of aquatic fauna. In this study, the effects of low temperature were studied on the functional state of juvenile golden pompano ( Trachinotus ovatus ) under low-temperature stress. The study was conducted at 28°C in the control group and 18°C in the cold group for 14 d to determine the intestinal tissue, digestive and antioxidant enzyme activities, and metabolites of juvenile fish. The results showed that: (1) the swelling degree of the muscle layer deepened and was congested with a longer low-temperature stress period. The folds were sparse, from slight swelling to shedding and deformation. The intestinal mucosa was necrotic and had vacuoles, and the number gradually increased. Serious erosion of the villi occurred. (2) The specific activities of digestive enzymes showed a downward trend. (3) The intestinal superoxide dismutase (SOD) activity, malondialdehyde (MDA) content, and glutathione peroxidase (GSH-Px) activity showed an upward trend. The intestinal catalase (CAT) activity showed a downward trend. (4) Compared with the control group, there were 28 metabolites in the cold group showing significant differences, among which Z, 11Z, 14Z-eicosatrienoic acid, stearic acid, and adrenic acid showed an upward trend. In contrast, spermidine and uracil showed a downward trend. Among the enriched metabolic pathways, the main differential pathways were unsaturated fatty acid biosynthesis, fatty acid biosynthesis, linoleic acid metabolism, pyrimidine metabolism, and β-alanine metabolism. According to metabolomic analysis, under low-temperature stress, the fish body improved the synthesis of unsaturated fatty acids and saturated fatty acids to adapt to a low-temperature environment and consumed spermidine to improve its immune ability to clear the peroxide generated by the synthesis of unsaturated fatty acids in the body so that the cells were protected from oxidative damage. After 14 days, low-temperature stress affected metabolites and enzyme activity indices in juvenile golden pompano. Low-temperature stress causes changes in intestinal antioxidants and digestive enzymes and damage intestinal tissues. As a result of this exploration of how low temperatures affect the juvenile golden pompano, the foundation is laid for future studies, such as the molecular mechanisms of low-temperature adaptation in fish species.

Selective recovery of rare earth elements and value-added chemicals from the Dicranopteris linearis bio-ore produced by agromining using green fractionation - Candie Xie; Ye Xiao; Chao He; Wen-Shen Liu; Ye-Tao Tang; Shizhong Wang; Antony van der Ent; Jean Louis Morel; Marie-Odile Simonnot; Rong-Liang Qiu (Journal of Hazardous Materials, 2023)

A novel multistage anoxic/aerobic process with sludge regeneration zone (R-MAO) for advanced nitrogen removal from domestic sewage - Lin Cao; Rong Sun; Wenyi Dong; Hongjie Wang; Zhongyi Dai; Xue Wang; Jin Xie; Hua Li (Journal of Environmental Sciences, 2023)

Characterization of gallic acid-Chinese yam starch biodegradable film incorporated with chitosan for potential use in pork preservation - Liyuan Rong; Xiaoyao Ji; Mingyue Shen; Xianxiang Chen; Xing Qi; Yulin Li; Jianhua Xie (Food Research International, 2023)

Origin of clay in granite intrusive contact zone and its influence on tunnel deformation and instability - Guo-Hua Zhang; Bo-Wen Zhang; Fei Tan; Zhong-Hou Liu; Jun-Peng Zou; Zhong-Zhi Xie; Jin-Quan Wu; Zhi-Ping Lin; Zhan-Rong Zhang (Engineering Geology, 2023)

Extraction and characterization of waxy and normal barley β-glucans and their effects on waxy and normal barley starch pasting and degradation properties and mash filtration rate - Qiao Li; Juan Liu; Huisheng Zhai; Zhihui Zhang; Rong Xie; Futong Xiao; Xingquan Zeng; Yuhong Zhang; Zhongyi Li; Zhifen Pan (Carbohydrate Polymers, 2023)

Community succession of microbial populations related to C N P S biological transformations regulates product maturity during cow-manure-driven composting - Xin Liu; Xiangmin Rong; Junyan Yang; Han Li; Wang Hu; Yong Yang; Guoliang Jiang; Rusheng Xiao; Xingxiang Deng; Guixian Xie; Gongwen Luo; Jiachao Zhang (Bioresource Technology, 2023)

Bacillus litorisediminis sp. nov., a Thermophilic Bacterium Isolated from Mangrove Sediment - Rong Tang; Shang Yang; Shuang Han; Cheng-Jie Xie; Guan-Min Huang; Manik Prabhu Narsing Rao; Guo-Hong Liu; Shun-Gui Zhou (Current Microbiology, 2023)

Fundidesulfovibrio agrisoli sp. nov., A Nitrogen-Fixing Bacterium Isolated from Rice Field - Shang Yang; Rong Tang; Shuang Han; Cheng-Jie Xie; Manik Prabhu Narsing Rao; Guo-Hong Liu; Shun-Gui Zhou (Current Microbiology, 2023)

Spatial distributions of intra-community tree species under topographically variable conditions - Ting Lv; Rong Zhao; Ning-jie Wang; Lei Xie; Yue-yao Feng; Yao Li; Hui Ding; Yan-ming Fang (Journal of Mountain Science, 2023)

A multicentre study on the incidence of respiratory viruses in children with community-acquired pneumonia requiring hospitalization in the setting of the zero-COVID policy in China - Ziheng Feng; Baoping Xu; Lili Zhong; Jing Chen; Jikui Deng; Zhengxiu Luo; Lingfeng Cao; Yu Tang; Changchong Li; Rong Jin; Li Deng; Yunxiao Shang; et al. (Archives of Virology, 2023)
Background Stringent nonpharmaceutical interventions (NPIs) have been implemented worldwide to combat the COVID-19 pandemic, and the circulation and seasonality of common respiratory viruses have subsequently changed. There have been few multicentre studies or comparisons of the prevalence of respiratory viruses accounting for community-acquired pneumonia (CAP) in hospitalized children between the pre-COVID period and the period after community and school reopening in the setting of the zero-COVID policy. Methods We included 1543 children with CAP who required hospitalization from November 1, 2020 to April 30, 2021 (period 1), and 629 children with the same conditions from November 1, 2018, to April 30, 2019 (period 2), in our study. All respiratory samples from these patients were screened for six respiratory viruses (respiratory syncytial virus [RSV], adenovirus [ADV], influenza A virus [Flu A], influenza B virus [Flu B], parainfluenza virus type 1 [PIV1], and parainfluenza virus type 3 [PIV3]) using a multiplex real-time PCR assay. Results and conclusions The median ages of the enrolled patients at the time of diagnosis were 1.5 years and 1.0 years for period 1 and period 2, respectively. In period 1, viral pathogens were detected in 50.3% (776/1543) of the enrolled patients. The most frequently identified viral pathogen was RSV (35.9%, 554/1543), followed by PIV3 (9.6%, 148/1543), PIV1 (3.6%, 56/1543), ADV (3.4%, 52/1543), Flu A (1.0%, 16/1543), and Flu B (0.8%, 13/1543). The total detection rates of these six viruses in the peak season of CAP were at the pre-COVID level. The prevalence of Flu A decreased dramatically, and circulation activity was low compared to pre-COVID levels, while the incidence of PIV3 increased significantly. There were no significant differences in the detection rates of RSV, ADV, Flu B, and PIV1 between the two periods. Our results showed that respiratory viruses accounted for CAP in hospitalized children at pre-COVID levels as communities and schools reopened within the zero-COVID policy, although the prevalence aetiology spectrum varied.

A novel nitrogen-fixing bacterium, Propionivibrio soli sp. nov. isolated from paddy soil - Cheng-Jie Xie; Rong Tang; Shang Yang; Shuang Han; Christopher Rensing; Guo-Hong Liu; Shun-Gui Zhou (Archives of Microbiology, 2023)

Functional insights of a two-component system sensor kinase GacS in a fish pathogen, Pseudomonas plecoglossicida - Su-Ming Zhou; Yan Wang; Feng-Ling Shu; Zhen Tao; Xiao Xie; Jia-Song Xie; Rong-Rong Ma; Fei Yin (Aquaculture, 2023)

A study on the correlation between intrauterine microbiota and uterine pyogenesis in dogs - Hui-Hua Zheng; Chong-Tao Du; Yu-Zhu Zhang; Chao Yu; Rong-Lei Huang; Xin-Yue Tang; Guang-Hong Xie (Theriogenology, 2023)

Alkali-catalyzed hydrothermal oxidation treatment of triclosan in soil: Mechanism, degradation pathway and toxicity evaluation - Yushuang Chen; Rui Shi; Hongjun Luo; Rong Zhang; Yafei Hu; Haijiao Xie; Neng-min Zhu (Science of The Total Environment, 2023)

Multicopper oxidases GbAO and GbSKS are involved in the Verticillium dahliae resistance in Gossypium barbadense - Fei Wang; Tianxin Lu; Liping Zhu; Aiping Cao; Shuangquan Xie; Xifeng Chen; Haitao Shen; Quanliang Xie; Rong Li; Jianbo Zhu; Xiang Jin; Hongbin Li (Journal of Plant Physiology, 2023)

Impacts of meteorological factors and ozone variation on crop yields in China concerning carbon neutrality objectives in 2060 - Beiyao Xu; Tijian Wang; Libo Gao; Danyang Ma; Rong Song; Jin Zhao; Xiaoguang Yang; Shu Li; Bingliang Zhuang; Mengmeng Li; Min Xie (Environmental Pollution, 2023)

Regulatory effects mediated by ulvan oligosaccharide and its zinc complex on lipid metabolism in high-fat diet-fed mice - Yongzhou Chi; Zhihua Wu; Chunying Du; Man Zhang; Xinyu Wang; Aowei Xie; Peng Wang; Rong Li (Carbohydrate Polymers, 2023)

Correction to: Description of two nitrogen‑fixing bacteria, Geomonas fuzhouensis sp. nov. and Geomonas agri sp. nov., isolated from paddy soils - Shang Yang; Guo-Hong Liu; Rong Tang; Shuang Han; Cheng-Jie Xie; Shun-Gui Zhou (Antonie van Leeuwenhoek, 2023)

Physiological and transcriptome analysis of Mytilus coruscus in response to Prorocentrum lima and microplastics - Xiao-wen Tang; Rong Yu; Mei-hua Fan; Zhi Yang; Zhi Liao; Zong-xin Yang; Chen-ying Xie; Yu-kun Xuan; Jian-xin Wang; Xiao-lin Zhang; Xiao-jun Yan (Frontiers in Marine Science, 2022)
Nowadays, diarrheic shellfish toxicity (DSP) toxin and microplastics (MPs) are commonly found in coastal waters worldwide. Due to their widespread use, their persistence and toxicity, they may induce adverse effects on Mytilus coruscus . However, the underlying toxic mechanisms of DSP and MPs on M. coruscus remain unclear. This study explored the physiological index and transcriptome change of the digestive gland of adult M. coruscus exposed for 3 days to polystyrene (PS) MPs (0.2 mg/L, 90-100 μm) and Prorocentrum lima alone or in combination. The results showed that the CAT activity and MDA content significantly increased, respiration rate and feeding rate significantly decreased. The combination of MPs and P. lima caused more structural damage to the rough surface endoplasmic reticulum and mitochondria in the digestive glands of M. coruscus . The transcriptome analysis showed that 485 and 220 genes were up- and down-regulated, respectively, after exposure to P. lima ; 1,989 up-regulated DEGs and 1,098 down-regulated DEGs were identified after exposure to MP treatment, and 1,004 up-regulated DEGs and 664 down-regulated DEGs were identified after exposure to the combination of P. lima and MPs. The DEGs were mainly enriched in the lysosome, mRNA surveillance pathway, carbon metabolism, the mTOR signaling pathway, the complement and coagulation cascades, and the TNF signaling pathway. The MP, P. lima exposure mainly induced the expression of RNA-binding protein musashi, serine/arginine repetitive matrix protein 1, low affinity immunoglobulin epsilon Fc receptor, toll-like receptor 2, caspase 7, calmodulin, E3 ubiquitin-protein ligase, serine/threonine-protein kinase PRP4, glutathione S-transferase, and heat shock 70 kDa protein. MPs and P. lima poison mainly influence the expression of RNA transport, immune related gene, apoptosis, signal related gene, and antioxidant gene change. The combination of MPs and P. lima has a synergistic toxic effect. This study provides a new insights into its physiological and molecular responses of M. coruscus to MPs and P. lima toxic exposure.

Impact of repeated intravenous infusions of umbilical cord–derived versus bone marrow–derived mesenchymal stem cells on angiogenesis in a pregnant experimentally induced deep venous thrombosis rat model - Xi Cheng; Weina Wang; Rong Du; Mu Zhang; Yuanyuan Xie; Weiwei Sun; Jingjing Ji; Baolan Sun; Yuquan Zhang (In Vitro Cellular & Developmental Biology - Animal, 2022)

Two ferric-reducing bacteria Geothrix terrae sp. nov. and Geothrix alkalitolerans sp. nov., isolated from paddy soil - Shuang Han; Rong Tang; Shang Yang; Cheng-Jie Xie; Manik Prabhu Narsing Rao; Guo-Hong Liu; Shun-Gui Zhou (Archives of Microbiology, 2022)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Genetic characteristics of human coronavirus HKU1 in mainland China during 2018 - Xiangpeng Chen; Yun Zhu; Qi Li; Gen Lu; Changchong Li; Rong Jin; Lei Li; Baoping Xu; Liwei Gao; Ju Yin; Zhengde Xie (Archives of Virology, 2022)

Neural Stem Cells Therapy for Ischemic Stroke: Progress and Challenges - Tong Zhao; Tongming Zhu; Liqian Xie; Yao Li; Rong Xie; Feng Xu; Hailiang Tang; Jianhong Zhu (Translational Stroke Research, 2022)

Hybrid brain model accurately predict human procrastination behavior - Zhiyi Chen; Rong Zhang; Jiawei Xie; Peiwei Liu; Chenyan Zhang; Jia Zhao; Justin Paul Laplante; Tingyong Feng (Cognitive Neurodynamics, 2022)

Occurrence, distribution, and ecological risk of organophosphorus flame retardants and their degradation products in water and upper sediment of two urban rivers in Shenzhen, China - Yunlang Liu; Zuoming Xie; Tingting Zhu; Chen Deng; XiuJuan Qi; Rong Hu; Jinglin Wang; Jianyi Chen (Environmental Science and Pollution Research, 2022)

Changes in amino acid and fatty acid composition during early development in cobia (Rachycentron canadum) - Jian-sheng Huang; Rong-xin Li; Rui-tao Xie; You-ming Chen; Jian-dong Zhang; Eric Amenyogbe; Gang Chen (Frontiers in Marine Science, 2022)
An estimation of the utilization of endogenous nutrients from the yolk sac that occurs during embryonic and early larval development can be a valuable approach to studying the nutritional requirements of fish larvae. In this study, fertilized eggs, embryos (before the membrane, 24 hours after fertilization), newly-hatched larvae (0-d-old), and open-mouthed larvae (3-day-old, unfed rotifers) samples of cobia ( Rachycentron canadum ) were collected to determine the amino acid and fatty acid profiles. Crude protein composition varies significantly for cobia during the different stages of development. The total amino acids, except for lysine(Lys), histidine (His), methionine(Met), serine(Ser), and glycine(Gly), had no significant change in the early development stage ( P > 0.05); the content of other six essential amino acids (EAA) and six non-essential amino acids (NEAA) was consistent with the changing trend of total essential amino acid. From hatching newly hatched larvae to open-mouthed larvae, except for Leu, Phe and Ser, decreased significantly ( P <0.05). From the utilization rate of FAA, the utilization rate of Lys and Leu was the highest (60.26%) and (52.21%) in the embryonic and endogenous nutritional stages, respectively. The water content of the open-mouthed larvae of cobia was significantly higher than that of the fertilized eggs, embryos, and newly hatched larvae ( P < 0.05). Three kinds of saturated fatty acids (SFA), five kinds of monounsaturated fatty acids (MUFA), and eight kinds of polyunsaturated fatty acids (PUFA) were detected in the dry samples of each developmental stage. Based on these results, juvenile cobia can thrive with a wide range of crude protein concentrations. Further refinement of commercial cobia production feeds would have beneficial consequences for economic and environmental concerns due to the positive impacts of optimizing the protein component as well as the ability to maintain the rapid growth rates. The results show that the larval development of cobia needs to consume large amounts of n3PUFA (especially DHA and EPA) to improve the larvae’s survival rate. Research methods will always have limitations when evaluating the relationship between early life nutrition interventions and well-being outcomes later in life. This study provides essential information regarding cobia larvae’s fatty acid requirements.

Spatiotemporal variation of the loose deposits in Baisha River Basin after the 2008 Wenchuan earthquake - Jiao-rong Lyu; Yu-hai Bao; Hang-yu Xie; Hong Li; Yun-hua Hu; Xiu-bin He (Journal of Mountain Science, 2022)

Synthesis and in vitro biological evaluation of novel dendrocandin analogue as potential anti-tumor agent - Jing-Yun Yan; Hao-Nan Yang; Ning Yang; Yin-Rong Xie; Xiu-Li Sun; Ye-Wei Huang; Cheng-Ting Zi; Xuan-Jun Wang; Jun Sheng (Natural Product Research, 2022)

Development of UPLC-MS/MS method for determining hainanmycin in foods of animal origin - Ke-xin Chi; Hang Yu; Ya-hui Guo; Yu-liang Cheng; Yun-fei Xie; Wei-rong Yao (Food Additives & Contaminants: Part A, 2022)

Sugar Product Diversification and Its Opportunities in China - Qi Wang; Cai-Feng Xie; Chang-Rong Shi; Yuan Li; Yu-Hao Shang; Chu-Xuan Hou; Fang-Xue Hang; Jian-Bin Li; Kai Li (Sugar Tech, 2022)

Metabolomics analysis of the potential toxicological mechanisms of diquat dibromide herbicide in adult zebrafish (Danio rerio) liver - Ye Xiao; Xiang Lin; Meilan Zhou; Tianyu Ren; Ruili Gao; Zhongqun Liu; Wenjing Shen; Rong Wang; Xi Xie; Yanting Song; Wenting Hu (Fish Physiology and Biochemistry, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Prediction of the sea buckthorn AQP gene structure and its spatiotemporal expression pattern under drought stress - Dan Zhang; Nanxiang Yang; Jiawei Dong; Cheng Wang; Qiangfeng Li; Rong Wang; Zhipeng Feng; Dejuan Xie; Guisheng Ye; Yuhua Ma (Journal of Plant Biochemistry and Biotechnology, 2022)

Analysis of Grain Yield Formation Components of Extra Heavy-Panicle-Type Mid-Season Indica Hybrid Rice - Xiaolong Zhong; Hafiz Athar Hussain; Bingbing Zhao; Manyu Huang; Saddam Hussain; Rong Xie; Linjun Cai; Han Yun; Guanghua He; Changwei Zhang (Journal of Plant Growth Regulation, 2022)

The comparative landscape of Chinese and foreign articles on the carbon footprint using bibliometric analysis - Rong Wu; Yundong Xie; Yezhu Wang; Zhi Li; Li Hou (Environmental Science and Pollution Research, 2022)

Phytoremediation of uranium-contaminated soil by perennial ryegrass (Lolium perenne L.) enhanced with citric acid application - Lishan Rong; Shiqi Zhang; Jiali Wang; Shiyou Li; Shuibo Xie; Guohua Wang (Environmental Science and Pollution Research, 2022)

Description of two nitrogen-fixing bacteria, Geomonas fuzhouensis sp. nov. and Geomonas agri sp. nov., isolated from paddy soils - Shang Yang; Guo-Hong Liu; Rong Tang; Shuang Han; Cheng-Jie Xie; Shun-Gui Zhou (Antonie van Leeuwenhoek, 2022)

Digoxin Ameliorates Glymphatic Transport and Cognitive Impairment in a Mouse Model of Chronic Cerebral Hypoperfusion - Jie Cao; Di Yao; Rong Li; Xuequn Guo; Jiahuan Hao; Minjie Xie; Jia Li; Dengji Pan; Xiang Luo; Zhiyuan Yu; Minghuan Wang; Wei Wang (Neuroscience Bulletin, 2022)

Eutrophication and predation mediate zooplankton diversity and network structure - Yun Li; Rong Wang; Haojie Su; Jianjun Wang; Ping Xie; Feizhou Chen (Limnology and Oceanography, 2022)
Anthropogenic activities such as eutrophication and fishing have prominent effects on freshwater ecosystems. However, the ways in which ecosystem function and biodiversity respond to multiple drivers from eutrophication and top‐down predation remains inconclusive. We studied zooplankton communities in 102 subtropical shallow lakes in the eastern plain of China and further examined the joint effects of nutrient enrichment and predation on biodiversity and ecological networks. We found that alpha diversity was negatively influenced by nutrient conditions (such as total phosphorus and total nitrogen [TN]), whereas beta diversity (β‐diversity) was positively related to nutrients and was also structured by omnivorous fish showing a unimodal pattern. Furthermore, the network skewness of zooplankton increased with nutrient enrichment, especially TN, and was negatively related to omnivorous fish. This skewness is more sensitive than β‐diversity, whereas negative skew is primarily caused by omnivorous fish. Our results demonstrated that top‐down effects were dominant for zooplankton communities and resulted in structural adjustment of zooplankton communities, mainly with an increase in fish predation. A negative skewed network indicates the presence of more generalist species and stronger connections among the zooplankton assemblages, as well as decreased β‐diversity.

Circ_0002711 knockdown suppresses cell growth and aerobic glycolysis by modulating miR-1244/ROCK1 axis in ovarian cancer - Weiquan Xie; Lu Liu; Chuanyong He; Min Zhao; Rong Ni; Zixiong Zhang; Chengyu Shui (Journal of Biosciences, 2021)

Effects of Zinc Smelting Waste Slag Treated with Root Organic Acids on the Liver of Zebrafish (Danio rerio) - Xiaorui Wang; Yonggui Wu; Rong Xie; Kaizhi Yang; Hongyue Wu; Tieyun Wang (Bulletin of Environmental Contamination and Toxicology, 2021)

The chemical profile and biological activity of different extracts of Sapindus mukorossi Gaertn. against Cutibacterium acnes - Min-Ping Wei; Jin-Dan Qiu; Lu Li; Yun-Fei Xie; Ya-Hui Guo; Hang Yu; Yu-Liang Cheng; He Qian; Wei-Rong Yao (Natural Product Research, 2021)

Isolation of two sesquiterpene glycosides from Sapindus mukorossi Gaertn. with cytotoxic properties and analysis of their mechanism based on network pharmacology - Min-ping Wei; Xiao-wen Zhu; Hang Yu; Yun-fei Xie; Ya-hui Guo; Yu-liang Cheng; He Qian; Wei-rong Yao (Natural Product Research, 2021)

Tree mycorrhizal effect on litter-leached DOC amounts and biodegradation is highly dependent on leaf habits in subtropical forests of southern China - Yi-Dong Ding; Xin-Yi Xie; Jing-Hao Ji; Qian-Qian Li; Jia-Wen Xu; Rong Mao (Journal of Soils and Sediments, 2021)

Efficient separation and recovery of Re(VII) from Re/U bearing acidic solutions using aminotriazole modified cellulose microsphere adsorbents - Di Wen; Rong Hua; Zhen Dong; Kangjun Xie; Wei Qi; Long Zhao (Environmental Science and Pollution Research, 2021)

Characteristics of expanded polystyrene microplastics on island beaches in the Pearl River Estuary: abundance, size, surface texture and their metals-carrying capacity - Qun Xie; Heng-Xiang Li; Lang Lin; Zhen-Liang Li; Jian-sheng Huang; Xiang-Rong Xu (Ecotoxicology, 2021)

Mystery of methamphetamine-induced autophagosome accumulation in hippocampal neurons: loss of syntaxin 17 in defects of dynein–dynactin driving and autophagosome–late endosome/lysosome fusion - Huaisha Xu; Yuanhui Zhu; Xufeng Chen; Tingyu Yang; Xi Wang; Xu Song; Xuexue Xie; Miaoyang Hu; Lei Jiang; Jie Cheng; Rong Gao; Jun Wang (Archives of Toxicology, 2021)

Surfactant-assisted adsorption of uranyl ions in aqueous solution on TiO2/polythiophene nanocomposite - Youqun Wang; Yinghui Xie; Zhiyang Zheng; Dejun Zeng; Ying Dai; Zhibin Zhang; Xiaohong Cao; Rong Zou; Yunhai Liu (Environmental Science and Pollution Research, 2021)

Retrospective surveillance of porcine circovirus 4 in pigs in Inner Mongolia, China, from 2016 to 2018 - Zhuo Ha; Chengdong Yu; Changzhan Xie; Guanyu Wang; Ying Zhang; Pengfei Hao; Jinfeng Li; Zhuoxin Li; Yanwei Li; Fulong Rong; Fulong Nan; He Zhang; et al. (Archives of Virology, 2021)

Genotypic variation in nitrogen utilization efficiency in oilseed rape is related to the coordination of leaf senescence and root N uptake during reproductive stage - Huiying He; Yuyu Xie; Anyu Zhao; Wencong Hu; Xiao Guo; Anthony J. Miller; Xiaoming Wu; Biyun Chen; Rong Zhang; Hui Tian; Yajun Gao (Plant and Soil, 2021)

Syntheses and anticancer activities of novel glucosylated (−)-epigallocatechin-3-gallate derivatives linked via triazole rings - Bo-Ya Shi; Ze-Hao Wang; Ning Zhang; Yin-Rong Xie; Xiu-Li Sun; Hao-Nan Yang; Yi-Long Wu; Cheng-Ting Zi; Xuan-Jun Wang; Jun Sheng (Medicinal Chemistry Research, 2021)

Long-term field evaluation and large-scale application of a Metarhizium anisopliae strain for controlling major rice pests - Guoxiong Peng; Jiaqin Xie; Rong Guo; Nemat O. Keyhani; Deyu Zeng; Puyun Yang; Yuxian Xia (Journal of Pest Science, 2021)

MiR-150-5p regulate T cell activation in severe aplastic anemia by targeting Bach2 - Yingmei Li; Jifeng Yu; Fang Wang; Rong Guo; Haizhou Xing; Yali Chen; Dandan Chen; Xinsheng Xie; Dingming Wan; Zhongxing Jiang (Cell and Tissue Research, 2021)

Chloroplast genomes of two Mediterranean Bupleurum species and the phylogenetic relationship inferred from combined analysis with East Asian species - Rong Huang; Xuena Xie; Fang Li; Enwei Tian; Zhi Chao (Planta, 2021)

Evolution of lithospheric mantle beneath the Maguan region, southwestern margin of the South China block based on mantle xenoliths in Miocene alkaline volcanic rocks - Zhipeng Xie; Keiko Hattori; Rong Wang; Jian Wang; Jiao Qianqian; Die Wang (Mineralogy and Petrology, 2021)

A teleconnection between sea surface temperature in the central and eastern Pacific and wintertime haze variations in southern China - Xugeng Cheng; Jane Liu; Tianliang Zhao; Sunling Gong; Xiangde Xu; Xiaoning Xie; Rong Wang (Theoretical and Applied Climatology, 2021)
Haze pollution in recent decades varies largely with both pollutant emissions and meteorological conditions. Using the discrete wavelet transform (DWT) method, we separate these two influences on haze variations in southern China in the time series of haze observations from 1981 to 2011. This helps us to identify the meteorological influence on interannual variation in haze occurrences in southern China and thus observe a teleconnection between the thermal forcing of sea surface temperature (SST) in the central and eastern Pacific and wintertime haze occurrences in southern China ( R = − 0.51, p < 0.05). The total haze days in winter is highest among all seasons over southern China and the climotological mean of number of winter haze days is 7.5 days for the region. Compared with the normal winters, the regional mean of the number of haze days in southern China is reduced by ~ 5 days in the winters with above-normal Niño3.4 SST (during El Niño phases), but increased by ~ 4 days in the winters with below-normal Niño3.4 SST (during La Niña phases). In the warm SST winters, the cumulative consequences of strong winds, more precipitation, and a more unstable atmosphere with an “upper colder and lower warmer” vertical pattern leading to more ascendance can all hinder haze formation, whereas in the cold SST winters, opposite meteorological conditions are favorable to haze formation. These meteorological conditions induced by anomalous SST make wintertime haze pollution in southern China vary from year to year to a large extent. This study suggests a strong sensitivity of winter haze occurrences in southern China to the viability of the SST in the central and eastern Pacific.

Controlled-release N fertilizer to mitigate ammonia volatilization from double-cropping rice - Chang Tian; Xuan Zhou; Zheli Ding; Qiang Liu; Guixian Xie; Jianwei Peng; Xiangming Rong; Yuping Zhang; Yong Yang; Mamdouh A. Eissa (Nutrient Cycling in Agroecosystems, 2021)
Controlled-release nitrogen fertilizer (CRNF) can effectively enhance crop yields and raise the efficiency of nitrogen fertilizer in agroecosystems. In the present study, the volatilization of NH 3 was determined by airflow enclosure chamber technique after the application of different CRNF rates in double-cropping rice fields in southern China for continuous 3 years. The early and late season rice (ESR and LSR) were cultivated each year. The results showed that the total NH 3 volatilization losses ranged from 25 to 56 kg N ha −1 in ESR and from 32 to 61 kg N ha −1 in LSR. The loss of N to the total applied N ranged from 12 to 29% in ESR and from 12 to 27% in LSR. The application of CRNF significantly reduced the cumulative NH 3 volatilization losses by 20–43% for ESR and by 20–32% for LSR compared with conventional urea application. CRNF in LSR was less effective to reduce NH 3 volatilization than that in ESR. Furthermore, the application of 80% of N rate in the form of CRNF gave higher grain yield and apparent nitrogen recovery efficiency (ANRE) than that of application of 100% of N rate from conventional urea. CRNF can effectively reduce NH 3 volatilization, and increase rice yield and ANRE. Considering higher price of CRNF, the application of CRNF at lower (20% applied N) rate than conventional urea in LSR may be a reasonable fertilization strategy for improving N use efficiency, environment effectiveness, and sustaining the development of rice production systems in double-cropping rice.

A Re-evaluation of the Taxonomy and Classification of the Type III Secretion System in a Pathogenic Bacterium Causing Soft Rot Disease of Pleurotus eryngii - Feng Xu; Hui Yan; Yu Liu; Shuang Zhao; Shuang Song; Tongtong Gu; Zhongjuan Song; Jianbo Xie; Chengbo Rong (Current Microbiology, 2021)

Outer inflammatory protein of Helicobacter pylori impacts IL-8 expression, adherence, cell apoptosis and cell cycle of gastric cells independent of its copy number - Qiaoyun Zhao; Wenzhu Yin; Rulin Zhao; Youhua Wang; Conghua Song; Huan Wang; Jianfang Rong; Fangfei Wang; Yong Xie (Medical Microbiology and Immunology, 2020)

SNP discovery in Mauremys reevesii and M. sinensis using restriction site-associated DNA sequence (RAD-seq) - Qiming Xie; Chaozhen Rong; Xilei Li; Nianyue Lai; Tiantian Chen; Qingqing Li; Shiping Su (Conservation Genetics Resources, 2020)

Comparison of the effects of deep and moderate neuromuscular block on respiratory system compliance and surgical space conditions during robot-assisted laparoscopic radical prostatectomy: a randomized clinical study - Shao-jun Zhu; Xiao-lin Zhang; Qing Xie; Yan-feng Zhou; Kui-rong Wang (Journal of Zhejiang University-SCIENCE B, 2020)

Light promotes jasmonate biosynthesis to regulate photomorphogenesis in Arabidopsis - Rong Yi; Jianbin Yan; Daoxin Xie (Science China Life Sciences, 2020)

Method for obtaining high-resolution velocity spectrum based on weighted similarity - Xing-Rong Xu; Qin Su; Jun-Fa Xie; Jing Wang; Long-Jiang Kou; Meng-Li Liu (Applied Geophysics, 2020)

High resolution UPLC-MS/MS method for simultaneous separation and determination of six flavonoids from semen cuscutae extract in rat plasma: application to comparative pharmacokinetic studies in normal and kidney-deficient rats - Wei Zhang; Zhi-Tian Fu; Yao Xie; Zhi-Wen Duan; Yu Wang; Rong-Hua Fan (Natural Product Research, 2020)

Polymer-coated urea effects on maize yield and nitrogen losses for hilly land of southern China - Yong Xie; Li Tang; Lan Yang; Yuping Zhang; Haixing Song; Chang Tian; Xiangmin Rong; Yongliang Han (Nutrient Cycling in Agroecosystems, 2020)

Reduced mineral fertilization coupled with straw return in field mesocosm vegetable cultivation helps to coordinate greenhouse gas emissions and vegetable production - Rong Huang; Jiang Liu; Xinhua He; Deti Xie; Jiupai Ni; Chang Xu; Yarong Zhang; En Ci; Zifang Wang; Ming Gao (Journal of Soils and Sediments, 2020)

Regulatory mechanisms and therapeutic potential of microglial inhibitors in neuropathic pain and morphine tolerance - Er-rong Du; Rong-ping Fan; Li-lou Rong; Zhen Xie; Chang-shui Xu (Journal of Zhejiang University-SCIENCE B, 2020)

Expression of the kisspeptin/gonadotropin-releasing hormone (GnRH) system in the brain of female Chinese sucker (Myxocyprinus asiaticus) at the onset of puberty - Shiping Su; Qingqing Li; Xilei Li; Chaozhen Rong; Qiming Xie (Fish Physiology and Biochemistry, 2020)

Effect of FIGF overexpression on liver cells transforming to insulin-producing cells - Yaqin He; Xiaoliang Xie; Xiaoyan Li; Shikuo Rong; Yukui Li; Zhenhui Lu (Journal of Biosciences, 2019)

Molecular cloning and characterization of genes related to the ethylene signal transduction pathway in pomegranate (Punica granatum L.) under different temperature treatments - Rong Huang; Wei Li; Xiao-Wan Guan; Biao Xie; Shui-Ming Zhang (Journal of Biosciences, 2019)

The complete chloroplast genome of the daimyo oak, Quercus dentata Thunb. - Hua-Lei Hu; Jing-Yu Zhang; Yu-Ping Li; Lu Xie; Dong-Bin Chen; Qun Li; Yan-Qun Liu; Shu-Rong Hui; Li Qin (Conservation Genetics Resources, 2019)

Impact of CYP2R1, CYP27A1 and CYP27B1 genetic polymorphisms controlling vitamin D metabolism on susceptibility to hepatitis C virus infection in a high-risk Chinese population - Jing-jing Yang; Hao-zhi Fan; Ting Tian; Meng-ping Wu; Chao-nan Xie; Peng Huang; Rong-bin Yu; Hong-Gang Yi; Yun Zhang; Jie Wang (Archives of Virology, 2019)

Ecological Risk Assessment of Neodymium and Yttrium on Rare Earth Element Mine Sites in Ganzhou, China - Chun-Mei Zhao; Xing Shi; Si-Qi Xie; Wen-Shen Liu; Er-Kai He; Ye-Tao Tang; Rong-Liang Qiu (Bulletin of Environmental Contamination and Toxicology, 2019)

Development of a loop-mediated isothermal amplification for rapid diagnosis of Aphelenchoides ritzemabosi - Dong-Wei Wang; Chun-Ling Xu; Zong-Shi Bai; Jun-Yi Li; Yu-Chun Han; Li-Rong Zhao; Hui Xie (European Journal of Plant Pathology, 2019)

Geological and geochemical characteristics of the Baogudi Carlin-type gold district (Southwest Guizhou, China) and their geological implications - Songtao Li; Yong Xia; Jianzhong Liu; Zhuojun Xie; Qinping Tan; Yimeng Zhao; Minghua Meng; Lijin Tan; Rong Nie; Zepeng Wang; Guanghong Zhou; Haiyan Guo (Acta Geochimica, 2019)

HL2 on chromosome 7D of wheat (Triticum aestivum L.) regulates both head length and spikelet number - Hongni Yao; Quan Xie; Shulin Xue; Jing Luo; Jikang Lu; Zhongxin Kong; Yongpan Wang; Wenling Zhai; Nan Lu; Rong Wei; Yang Yang; Yuzhou Han; et al. (Theoretical and Applied Genetics, 2019)

Reduced thiamine binding is a novel mechanism for TPK deficiency disorder - Wenjie Huang; Jiao Qin; Dingdong Liu; Yan Wang; Xiaofei Shen; Na Yang; Hui Zhou; Xiao-Tang Cai; Zhi-Ling Wang; Dan Yu; Rong Luo; Qingxiang Sun; et al. (Molecular Genetics and Genomics, 2019)

Relationship between polymorphisms of the lipid metabolism-related gene PLA2G16 and risk of colorectal cancer in the Chinese population - Xiao-Nv Xie; Jing Yu; Li-Hua Zhang; Zhi-Ying Luo; Dong-Sheng Ouyang; Ling-Jie Zheng; Chun-Yang Wang; Li Yang; Ling Chen; Zhi-Rong Tan (Functional & Integrative Genomics, 2019)

Underestimated ecosystem carbon turnover time and sequestration under the steady state assumption: A perspective from long‐term data assimilation - Rong Ge; Honglin He; Xiaoli Ren; Li Zhang; Guirui Yu; T. Luke Smallman; Tao Zhou; Shi‐Yong Yu; Yiqi Luo; Zongqiang Xie; Silong Wang; Huimin Wang; et al. (Global Change Biology, 2019)
It is critical to accurately estimate carbon (C) turnover time as it dominates the uncertainty in ecosystem C sinks and their response to future climate change. In the absence of direct observations of ecosystem C losses, C turnover times are commonly estimated under the steady state assumption ( SSA ), which has been applied across a large range of temporal and spatial scales including many at which the validity of the assumption is likely to be violated. However, the errors associated with improperly applying SSA to estimate C turnover time and its covariance with climate as well as ecosystem C sequestrations have yet to be fully quantified. Here, we developed a novel model‐data fusion framework and systematically analyzed the SSA ‐induced biases using time‐series data collected from 10 permanent forest plots in the eastern China monsoon region. The results showed that (a) the SSA significantly underestimated mean turnover times ( MTT s) by 29%, thereby leading to a 4.83‐fold underestimation of the net ecosystem productivity ( NEP ) in these forest ecosystems, a major C sink globally; (b) the SSA ‐induced bias in MTT and NEP correlates negatively with forest age, which provides a significant caveat for applying the SSA to young‐aged ecosystems; and (c) the sensitivity of MTT to temperature and precipitation was 22% and 42% lower, respectively, under the SSA . Thus, under the expected climate change, spatiotemporal changes in MTT are likely to be underestimated, thereby resulting in large errors in the variability of predicted global NEP . With the development of observation technology and the accumulation of spatiotemporal data, we suggest estimating MTT s at the disequilibrium state via long‐term data assimilation, thereby effectively reducing the uncertainty in ecosystem C sequestration estimations and providing a better understanding of regional or global C cycle dynamics and C‐climate feedback.

The Extraction of Urban Surface Water from Hyperspectral Data Based on Spectral Indices - Jiawei Yang; Chengyu Liu; Rong Shu; Feng Xie (Journal of the Indian Society of Remote Sensing, 2018)

Late spring soil moisture variation over the Tibetan Plateau and its influences on the plateau summer monsoon - Juan Zhou; Jun Wen; Rong Liu; Xin Wang; Yan Xie (International Journal of Climatology, 2018)
Based on the European Centre for Medium‐Range Weather Forecasts (ECMWF) ERA‐Interim reanalysis data from 1979 to 2016, an index for Tibetan Plateau (TP) soil moisture ( I TPSM ), which could represent inter‐annual variation in spring soil moisture, is defined after removing the linear trend in soil moisture. The late spring soil moisture variation over the TP and its influences on the plateau summer monsoon are analysed. The results show that the TP soil moisture variation is non‐uniform, and spring soil moisture over the northeastern TP shows an increasing trend, while the western TP (especially the peripheral area) renders a significantly decreasing trend. When the I TPSM shows positive (negative) anomalies (i.e., spring soil moisture over the northeastern TP is higher (lower), soil moisture over the western TP is lower (higher) than normal), the plateau summer monsoon may be stronger (weaker). Anomalous variations in spring TP soil moisture can eventually affect the plateau summer monsoon by changing atmospheric circulation, diabatic heating, and water vapour transportation. It is found that when the I TPSM exhibits positive anomalies, diabatic heating over the centre and eastern TP is remarkably enhanced, and warm and humid moisture from the Bay of Bengal and Arabian Sea and cold air from high latitudes merge over the central and eastern TP; coupled with lower‐level convergence and upper‐level divergence, all these contribute to an increase in plateau summer monsoonal precipitation. When the I TPSM shows negative anomalies, diabatic heating over the centre and eastern TP is weakened, the anomalous cyclone to the south of the TP hinders warm and humid air flows transportation to the TP, and the anomalous anticyclone to the southeast of Lake Baikal weakens cold air to the south; coupled with weakened convergence and upwards motion, these factors all lead to a decrease in plateau summer monsoonal precipitation.

Genetic variability of wildlife-derived Sarcoptes scabiei determined by the ribosomal ITS-2 and mitochondrial 16S genes - Chun-Yan Li; Yin Sun; Yue Xie; Xuan Zhou; Xiao-Bin Gu; Wei-Ming Lai; Xue-Rong Peng; Guangyou Yang (Experimental and Applied Acarology, 2018)

Transcriptome analysis of differentially expressed genes in rabbits’ ovaries by digital gene-expression profiling - Tao Huang; Ya-dong Wang; Ming-ming Xue; Xue Feng; Cai-Xia Sun; An-si Wang; Shu-yu Xie; Meng Zhang; Gui-Rong Sun; Ming Li (Genes & Genomics, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Pleiotropic effects of the wheat domestication gene Q on yield and grain morphology - Quan Xie; Na Li; Yang Yang; Yulong Lv; Hongni Yao; Rong Wei; Debbie L. Sparkes; Zhengqiang Ma (Planta, 2018)

Spinal CCL2 Promotes Central Sensitization, Long-Term Potentiation, and Inflammatory Pain via CCR2: Further Insights into Molecular, Synaptic, and Cellular Mechanisms - Rou-Gang Xie; Yong-Jing Gao; Chul-Kyu Park; Ning Lu; Ceng Luo; Wen-Ting Wang; Sheng-Xi Wu; Ru-Rong Ji (Neuroscience Bulletin, 2018)

p70S6K activation promotes the transdifferentiation of fibroblasts to myofibroblasts in pterygium tissue growth on the cornea - Xin-Rong Zhao; Ming-Chang Zhang; Hua-Tao Xie; Nan Ji; Le-Tian Sun (Biotechnology Letters, 2018)

Exploration of the formation mechanism and source attribution of ambient ozone in Chongqing with an observation-based model - Rong Su; KeDing Lu; JiaYan Yu; ZhaoFeng Tan; MeiQing Jiang; Jing Li; ShaoDong Xie; YuSheng Wu; LiMin Zeng; ChongZhi Zhai; YuanHang Zhang (Science China Earth Sciences, 2018)

Concentrations and Exposure Evaluation of Metals in Diverse Food Items from Chengdu, China - Rong Wang; Bifeng Zhong; Lu Pi; Fuyu Xie; Mengqin Chen; Sanglan Ding; Shijun Su; Zhi Li; Zhiwei Gan (Archives of Environmental Contamination and Toxicology, 2018)

Injectable Sustained-Release Depots of PLGA Microspheres for Insoluble Drugs Prepared by hot-Melt Extrusion - Yuting Guo; Yunning Yang; Luying He; Rong Sun; Chenguang Pu; Bin Xie; Haibing He; Yu Zhang; Tian Yin; Yanjiao Wang; Xing Tang (Pharmaceutical Research, 2017)

Development of a Time-Resolved Fluorescence Immunoassay for the Diagnosis of Hepatocellular Carcinoma Based on the Detection of Glypican-3 - Juan-Juan Chen; Chun-Mei Xie; Cong-Rong Wang; Yong Wan; Zhi-Ning Dong; Ming Li; Wei-Wen Xu (Journal of Fluorescence, 2017)

The contribution of component variation and phytoplankton growth to the distribution variation of chromophoric dissolved organic matter content in a mid-latitude subtropical drinking water source reservoir for two different seasons - Qiyuan Sun; Juan Jiang; Yuyi Zheng; Feifeng Wang; Chunshan Wu; Rong-rong Xie (Environmental Science and Pollution Research, 2017)

Green Synthesis of Sucrose Laurate Under Different Ultrasonic Frequencies - Fang-xue Hang; Chang-rong Shi; Yong-shi Xu; Hai-qin Lu; Cai-feng Xie; Kai Li (Sugar Tech, 2017)

Fruit and vegetable consumption and risk of cardiovascular disease: A meta-analysis of prospective cohort studies - Jian Zhan; Yu-Jian Liu; Long-Biao Cai; Fang-Rong Xu; Tao Xie; Qi-Qiang He (Critical Reviews in Food Science and Nutrition, 2017)

Cloning and expression analysis of zygote arrest 1 (Zar1) in New Zealand white rabbits - DAN WANG; SHU-YU XIE; WEI ZHANG; CAI-XIA SUN; TAO HUANG; AN-SI WANG; XUE-LEI HAN; GUI-RONG SUN; MING LI (Journal of Genetics, 2017)

Pilot Demonstration of Ceramic Membrane Ultrafiltration of Sugarcane Juice for Raw Sugar Production - Wen Li; Guo-Qing Ling; Chang-Rong Shi; Kai Li; Hai-Qin Lu; Fang-Xue Hang; Yu Zhang; Cai-Feng Xie; Deng-Jun Lu; Hong Li (Sugar Tech, 2017)

Exploration of cultivable fungal communities in deep coal‐bearing sediments from ∼1.3 to 2.5 km below the ocean floor - Chang‐Hong Liu; Xin Huang; Tian‐Ning Xie; Ning Duan; Ya‐Rong Xue; Tan‐Xi Zhao; Mark A. Lever; Kai‐Uwe Hinrichs; Fumio Inagaki (Environmental Microbiology, 2017)
Summary Although subseafloor sediments are known to harbour a vast number of microbial cells, the distribution, diversity, and origins of fungal populations remain largely unexplored. In this study, we cultivated fungi from 34 of 47 deep coal‐associated sediment samples collected at depths ranging from 1289 to 2457 m below the seafloor (mbsf) off the Shimokita Peninsula, Japan (1118 m water depth). We obtained a total of 69 fungal isolates under strict contamination controls, representing 61 Ascomycota (14 genera, 23 species) and 8 Basidiomycota (4 genera, 4 species). Penicillium and Aspergillus relatives were the most dominant genera within the Ascomycetes, followed by the members of genera Cladosporium , Hamigera , Chaetomium , Eutypella , Acremonium , Aureobasidium , Candida , Eurotium , Exophiala , Nigrospora , Bionectria and Pseudocercosporella . Four Basidiomycota species were identified as genera Schizophyllum , Irpex , Bjerkandera and Termitomyces . Among these isolates, Cladosporium sphaerospermum and Aspergillus sydowii relatives were isolated from a thin lignite coal‐sandstone formation at 2457 mbsf. Our results indicate that these cultivable fungal populations are indigenous, originating from past terrigenous environments, which have persisted, possibly as spores, through ∼20 million years of depositional history.

Characterization of harpinXoo induced hypersensitive responses in non host plant, tobacco - Linlin Xie; Yue Liu; Hui Wang; Wenbo Liu; Rong Di; Weiguo Miao; Fucong Zheng (Journal of Plant Biochemistry and Biotechnology, 2017)

EGFL7-overexpressing epidermal stem cells promotes fibroblast proliferation and migration via mediating cell adhesion and strengthening cytoskeleton - Rong-Hua Yang; Shao-Hai Qi; Shu-Bin Ruan; Ze-Peng Lin; Yan Lin; Feng-Gang Zhang; Xiao-Dong Chen; Ju-Lin Xie (Molecular and Cellular Biochemistry, 2016)

Identification and Characterization of the Lysine-Rich Matrix Protein Family in Pinctada fucata: Indicative of Roles in Shell Formation - Jian Liang; Jun Xie; Jing Gao; Chao-Qun Xu; Yi Yan; Gan-Chu Jia; Liang Xiang; Li-Ping Xie; Rong-Qing Zhang (Marine Biotechnology, 2016)

Syndecan-4 regulates the bFGF-induced chemotactic migration of endothelial cells - Ran Li; Han Wu; Jun Xie; Guannan Li; Rong Gu; Lina Kang; Lian Wang; Biao Xu (Journal of Molecular Histology, 2016)

Combinatorial anticancer effects of curcumin and sorafenib towards thyroid cancer cells via PI3K/Akt and ERK pathways - Junjia Zhang; Jichun Yu; Rong Xie; Wanzhi Chen; Yunxia Lv (Natural Product Research, 2016)

A new dimeric anthraquinone from endophytic Talaromyces sp. YE3016 - Xiao-Song Xie; Xiao-Wei Fang; Rong Huang; Shou-Peng Zhang; Hong-Xia Wei; Shao-Hua Wu (Natural Product Research, 2016)

Comparison of DNA methylation in the developing seeds of yellow- and black-seeded Brassica napus through MSAP analysis - Y. Wang; H. Rong; T. Xie; J. Jiang; J. Wu; Y. Wang (Euphytica, 2016)

Distribution and contamination assessment of heavy metals in soils from tidal flat, oil exploitation zone and restored wetland in the Yellow River Estuary - Xinying Yao; Rong Xiao; Ziwen Ma; Ying Xie; Mingxiang Zhang; Feihai Yu (Wetlands, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Microbial community characteristics during simultaneous nitrification-denitrification process: effect of COD/TP ratio - Jian Zhang; Wenlin Jia; Rong Wang; Huu Hao Ngo; Wenshan Guo; Huijun Xie; Shuang Liang (Environmental Science and Pollution Research, 2016)

Genome-wide comparison of ferritin family from Archaea, Bacteria, Eukarya, and Viruses: its distribution, characteristic motif, and phylogenetic relationship - Lina Bai; Ting Xie; Qingqing Hu; Changyan Deng; Rong Zheng; Wanping Chen (The Science of Nature, 2015)

Role of the phase transition of intraseasonal oscillation on the South China Sea summer monsoon onset - Xie Shao; Ping Huang; Rong-Hui Huang (Climate Dynamics, 2015)

Inversion of vegetation height from PolInSAR using complex least squares adjustment method - HaiQiang Fu; ChangCheng Wang; JianJun Zhu; QingHua Xie; Rong Zhao (Science China Earth Sciences, 2015)

Effects on Pharmacokinetics of Propranolol and Other Factors in Rats After Acute Exposure to High Altitude at 4,010 m - Li Wenbin; Wang Rong; Xie Hua; Zhang Juanhong; Wu Xiaoyu; Jia Zhengping (Cell Biochemistry and Biophysics, 2015)

Transformation of the endophytic fungus Acremonium implicatum with GFP and evaluation of its biocontrol effect against Meloidogyne incognita - Yu-Rong Yao; Xue-Liang Tian; Bao-Ming Shen; Zhen-Chuan Mao; Guo-hua Chen; Bing-Yan Xie (World Journal of Microbiology and Biotechnology, 2015)

Esthetic Management of Mucogingival Defects After Excision of Epulis Using Laterally Positioned Flaps - Yu-feng Xie; Rong Shu; Jie-lei Qian; Zhi-kai Lin; Georgios E. Romanos (Cell Biochemistry and Biophysics, 2015)

Biomechanics of pelvic organ prolapse - Shuang Ren; Bing Xie; JianLiu Wang; QiGuo Rong (Science China Life Sciences, 2015)

OsEMF2b Acts as a Regulator of Flowering Transition and Floral Organ Identity by Mediating H3K27me3 Deposition at OsLFL1 and OsMADS4 in Rice - Shiyong Xie; Min Chen; Rong Pei; Yidan Ouyang; Jialing Yao (Plant Molecular Biology Reporter, 2015)

Design and applications of bifunctional cinnamide derivatives as potential antimycobacterial agents with few hepatotoxic effects - Zheng-Rong Wu; De-Juan Zhi; Li-Fang Zheng; Jian-Ying Li; Yang Li; Qing-Jian Xie; Na Feng; Yan-Fang Bao; Qi-Yu Gao; Ying Song; Hong-Yu Li (Medicinal Chemistry Research, 2015)

An improved SCGM(1,m) model for multi-point deformation analysis - Qi-jie Wang; Chang-cheng Wang; Rong-an Xie; Xin-qing Zhang; Jian-jun Zhu (Geosciences Journal, 2014)

Analysis on the association between PPARα/γ polymorphisms and lipoprotein(a) in a Chinese Han population - Hui-Jian Xie; Bo Hai; Ming Wu; Qiu Chen; Meng-Meng Liu; Chen Dong; Zhi-Rong Guo (Molecular Genetics and Genomics, 2014)

Assessing the real value of farmland in China - Rong Hu; Dao-chi Qiu; De-ti Xie; Xin-ya Wang; Lin Zhang (Journal of Mountain Science, 2014)

Cloning and expression analysis on a homolog of spermatogonial stem-cell renewal factor in Fenneropenaeus chinensis - Rong Wen; Fuhua Li; Yusu Xie; Shihao Li; Chengsong Zhang; Kuijie Yu; Jianhai Xiang (Invertebrate Reproduction & Development, 2014)

Regulatory effect of AMP-activated protein kinase on pulmonary hypertension induced by chronic hypoxia in rats: in vivo and in vitro studies - Xiaoying Huang; Rong Fan; Yuanyuan Lu; Chang Yu; Xiaomei Xu; Xie Zhang; Panpan Liu; Shuangquan Yan; Chun Chen; Liangxing Wang (Molecular Biology Reports, 2014)

Phagocytic Removal of Neuronal Debris by Olfactory Ensheathing Cells Enhances Neuronal Survival and Neurite Outgrowth via p38MAPK Activity - Bao-Rong He; Song-Tao Xie; Ming-Mei Wu; Ding-Jun Hao; Hao Yang (Molecular Neurobiology, 2014)

Streptomycin inhibits electrophysiological changes induced by stretching of chronically infarcted rat hearts - Jun-xian Cao; Lu Fu; Qian-ping Gao; Rong-sheng Xie; Fan Qu (Journal of Zhejiang University-SCIENCE B, 2014)

Comparative genomics of the marine bacterial genus G laciecola reveals the high degree of genomic diversity and genomic characteristic for cold adaptation - Qi‐Long Qin; Bin‐Bin Xie; Yong Yu; Yan‐Li Shu; Jin‐Cheng Rong; Yan‐Jiao Zhang; Dian‐Li Zhao; Xiu‐Lan Chen; Xi‐Ying Zhang; Bo Chen; Bai‐Cheng Zhou; Yu‐Zhong Zhang (Environmental Microbiology, 2014)
Summary To what extent the genomes of different species belonging to one genus can be diverse and the relationship between genomic differentiation and environmental factor remain unclear for oceanic bacteria. With many new bacterial genera and species being isolated from marine environments, this question warrants attention. In this study, we sequenced all the type strains of the published species of G laciecola , a recently defined cold‐adapted genus with species from diverse marine locations, to study the genomic diversity and cold‐adaptation strategy in this genus. The genome size diverged widely from 3.08 to 5.96 M b, which can be explained by massive gene gain and loss events. Horizontal gene transfer and new gene emergence contributed substantially to the genome size expansion. The genus G laciecola had an open pan‐genome. Comparative genomic research indicated that species of the genus G laciecola had high diversity in genome size, gene content and genetic relatedness. This may be prevalent in marine bacterial genera considering the dynamic and complex environments of the ocean. Species of G laciecola had some common genomic features related to cold adaptation, which enable them to thrive and play a role in biogeochemical cycle in the cold marine environments.

Early lethality of shRNA-transgenic pigs due to saturation of microRNA pathways - Zhen Dai; Rong Wu; Yi-cheng Zhao; Kan-kan Wang; Yong-ye Huang; Xin Yang; Zi-cong Xie; Chang-chun Tu; Hong-sheng Ouyang; Tie-dong Wang; Da-xin Pang (Journal of Zhejiang University-SCIENCE B, 2014)

Isolation an Aldehyde Dehydrogenase Gene from Metagenomics Based on Semi-nest Touch-Down PCR - Rong Chen; Chenglu Li; Xiaolin Pei; Qiuyan Wang; Xiaopu Yin; Tian Xie (Indian Journal of Microbiology, 2014)

Determination of Concentration of Methotrexate Enantiomers in Intracellular and Extracellular Fluids of HepG2 Cells by Liquid Chromatography–Tandem Mass Spectrometry - Rong Wang; Lifang Guo; Hua Xie; Juanhong Zhang; Xiaoyun Li; Wenbing Li; Jianfeng Wang; Xiaoyu Wu; Zhengping Jia (Cell Biochemistry and Biophysics, 2013)

Isolation and characterization of fifteen polymorphic tetranucleotide microsatellite loci in Schizopygopsis younghusbandi Regan - Huan Zheng; Gui-Rong Zhang; Shan-Shan Guo; Kai-Jian Wei; Cong-Xin Xie; Tai-Ming Ge (Conservation Genetics Resources, 2013)

Neuroprotective effects of flavonoids extracted from licorice on kainate-induced seizure in mice through their antioxidant properties - Ling-hui Zeng; Hua-dan Zhang; Cai-ju Xu; Yu-jia Bian; Xue-jiao Xu; Qiang-min Xie; Rong-hua Zhang (Journal of Zhejiang University-SCIENCE B, 2013)

Discovery of a novel esterase subfamily sharing an identified arm sequence (ArmEst) by gene-specific metagenomic PCR - Ao Zhang; Rong Zhao; Peng Jin; Lifang Ma; Xiaolong Xiong; Tian Xie; Xiaolin Pei; Li Yu; Xiaopu Yin; Qiuyan Wang (Biotechnology Letters, 2013)

Immobilization of trace metals by phosphates in contaminated soil near lead/zinc mine tailings evaluated by sequential extraction and TCLP - Wei-Hong Wu; Zheng-Miao Xie; Jian-Ming Xu; Fan Wang; Jia-Chun Shi; Rong-Bin Zhou; Zan-Fang Jin (Journal of Soils and Sediments, 2013)

Addition of Co2+ to culture medium decides the functional expression of a recombinant nitrile hydratase in Escherichia coli - Xiaolin Pei; Qiuyan Wang; Chenglu Li; Xiaopu Yin; Rong Chen; Tian Xie (Biotechnology Letters, 2013)

Differences in oxidative stress, antioxidant systems, and microscopic analysis between regenerating callus-derived protoplasts and recalcitrant leaf mesophyll-derived protoplasts of Citrus reticulata Blanco - Xiaoyong Xu; Gaisheng Xie; Li He; Jiaojiao Zhang; Xiaoling Xu; Rong Qian; Guohua Liang; Ji-Hong Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

Pharmacokinetics Study of Amoxycillin and Clavulanic acid (8:1)-A New Combination in Healthy Chinese Adult Male Volunteers Using the LC–MS/MS Method - Juanhong Zhang; Yinfu Wang; Hua Xie; Rong Wang; Zhengping Jia; Xiandong Men; Liting Xu; Qiang Zhang (Cell Biochemistry and Biophysics, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

Gene cloning and functional analysis of yellow green leaf3 (ygl3) gene during the whole-plant growth stage in rice - Xiaoqing Tian; Yinghua Ling; Likui Fang; Peng Du; Xianchun Sang; Fangming Zhao; Yunfeng Li; Rong Xie; Guanghua He (Genes & Genomics, 2013)

Association of interleukin-1 gene polymorphisms with multiple sclerosis: a meta-analysis - Jian Huang; Zi-Kang Xie; Rong-Bin Lu; Zheng-Fu Xie (Inflammation Research, 2013)

Nitrogen transformations and balance in constructed wetlands for slightly polluted river water treatment using different macrophytes - Haiming Wu; Jian Zhang; Rong Wei; Shuang Liang; Cong Li; Huijun Xie (Environmental Science and Pollution Research, 2013)

Tetrandrine citrate eliminates imatinib-resistant chronic myeloid leukemia cells in vitro and in vivo by inhibiting Bcr-Abl/β-catenin axis - Xiao-hua Xu; Yi-chao Gan; Gen-bo Xu; Ting Chen; Hong Zhou; Jin-fen Tang; Ying Gu; Fei Xu; Ying-ying Xie; Xiao-ying Zhao; Rong-zhen Xu (Journal of Zhejiang University-SCIENCE B, 2012)

Identification and molecular cytology analysis of cold tolerance introgression lines derived from Oryza sativa L. mating with O. rufipogon Griff. - Xiang-Dong Luo; Liang-Fang Dai; Juan-Fang Cao; Shui-Rong Jian; Ya-Ling Chen; Biao-Lin Hu; Jian-Kun Xie (Euphytica, 2012)

Structural determination of two new triterpenoid saponins acylated with monoterpenic acid from Gymnocladus chinensis Baill. - Wen Qi; Dan Yuan; Lian-Mei Yang; Ke-Hui Xie; Tian-Zhi Cai; Rong Yang; Hong-Zheng Fu (Natural Product Research, 2012)

Molecular characterization of the PpMADS1 gene from peach - Cui Li; Hua Xie; Lin Zhang; Yong Xu; Yun-Fu Li; Rong-Cai Ma (Tree Genetics & Genomes, 2012)

The expression of a new HD-Zip II gene, MSHB1, involving the inhibitory effect of thidiazuron on somatic embryogenic competence in alfalfa (Medicago sativa L. cv. Jinnan) callus - Xin Hu; Chun-Rong Zhang; Hui Xie; Xia Huang; Yun-Feng Chen; Xue-Lin Huang (Acta Physiologiae Plantarum, 2012)

L-Type Cav1.2 Calcium Channel is Involved in 6-Hydroxydopamine-Induced Neurotoxicity in Rats - Rong Wang; Zegang Ma; Jun Wang; Junxia Xie (Neurotoxicity Research, 2012)

Genetic Overlap in the Quantitative Resistance of Rice at the Seedling and Adult Stages to Xanthomonas oryzae pv. oryzae - Yong-Li Zhou; Xue-Wen Xie; Mei-Rong Xu; Jin-Ping Zang; Ling-Hua Zhu; Jian-Long Xu; Zhi-Kang Li (Journal of Plant Biology, 2012)

[11C]DAC-PET for Noninvasively Monitoring Neuroinflammation and Immunosuppressive Therapy Efficacy in Rat Experimental Autoimmune Encephalomyelitis Model - Lin Xie; Tomoteru Yamasaki; Naotsugu Ichimaru; Joji Yui; Kazunori Kawamura; Katsushi Kumata; Akiko Hatori; Norio Nonomura; Ming-Rong Zhang; Xiao-Kang Li; Shiro Takahara (Journal of Neuroimmune Pharmacology, 2012)

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Erratum to: Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Phenotypic and molecular characterization of rhizobacterium Burkholderia sp. strain R456 antagonistic to Rhizoctonia solani, sheath blight of rice - Bin Li; Bao-Ping Liu; Rong-Rong Yu; Miao-Miao Lou; Yan-Li Wang; Guan-Lin Xie; Hong-Ye Li; Guo-Chang Sun (World Journal of Microbiology and Biotechnology, 2011)

Analysis of variable sites between two complete South China tiger (Panthera tigris amoyensis) mitochondrial genomes - Wenping Zhang; Bisong Yue; Xiaofang Wang; Xiuyue Zhang; Zhong Xie; Nonglin Liu; Wenyuan Fu; Yaohua Yuan; Daqing Chen; Danghua Fu; Bo Zhao; Yuzhong Yin; et al. (Molecular Biology Reports, 2011)

Discovering the distinct inhibitory effects between C4-epimeric glycosyl amino acids: new insight into the development of protein tyrosine phosphatase inhibitors - Xiao-Peng He; Cui Li; Zhi-Zhou Wang; Li-Xin Gao; Xiao-Xin Shi; Yun Tang; Juan Xie; Jia Li; Guo-Rong Chen; Kaixian Chen (Glycoconjugate Journal, 2011)

Tongxinluo promotes mesenchymal stem cell tube formation in vitro - Xin-yang Hu; Wen-xia Wang; Min-jia Yu; Xian-bao Liu; Rong-rong Wu; Feng Gao; Xin Huang; Jiang Cao; Xiao-jie Xie; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2011)

Characterization of a ZmSERK gene and its relationship to somatic embryogenesis in a maize culture - Suzhi Zhang; Xinggui Liu; Yueai Lin; Guangning Xie; Fengling Fu; Hailan Liu; Jing Wang; Shibin Gao; Hai Lan; Tingzhao Rong (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Kinetic analysis of γ-glutamyltransferase reaction process for measuring activity via an integration strategy at low concentrations of γ-glutamyl p-nitroaniline - Zhi-rong Li; Yin Liu; Xiao-lan Yang; Jun Pu; Bei-zhong Liu; Yong-hua Yuan; Yan-ling Xie; Fei Liao (Journal of Zhejiang University-SCIENCE B, 2011)

Efficacy and safety of escitalopram versus citalopram in major depressive disorder: a 6-week, multicenter, randomized, double-blind, flexible-dose study - Jian-Jun Ou; Guang-Lei Xun; Ren-Rong Wu; Le-Hua Li; Mao-Sheng Fang; Hong-Geng Zhang; Shi-Ping Xie; Jian-Guo Shi; Bo Du; Xue-Qin Yuan; Jing-Ping Zhao (Psychopharmacology, 2011)

Simvastatin attenuates TNF-α-induced growth inhibition and apoptosis in murine osteoblastic MC3T3-E1 cells - Yun-mei Yang; Wei-dong Huang; Qiang-min Xie; Zhe-rong Xu; Qi-jiang Zhao; Xi-mei Wu; Fen-fen Li; Xin-wei Dong (Inflammation Research, 2010)

Detection of survivin-expressing circulating cancer cells in the peripheral blood of patients with esophageal squamous cell carcinoma and its clinical significance - Mei Cao; Shang-Mian Yie; Sheng-Min Wu; Shu Chen; Be Lou; Xu He; Shang-Rong Ye; Ke Xie; Lin Rao; En Gao; Nai-Yao Ye (Clinical & Experimental Metastasis, 2009)

Hydraulic pressure inducing renal tubular epithelial-myofibroblast transdifferentiation in vitro - Fei-yan Li; Xi-sheng Xie; Jun-ming Fan; Zi Li; Jiang Wu; Rong Zheng (Journal of Zhejiang University-SCIENCE B, 2009)

The mixture of procyanidins extracted from the lotus seed pod and bilobalide ameliorates scopolamine-induced memory impairment in mice - Li Zhang; Ji-Qu Xu; Shuang Rong; Bi-Jun Xie; Zhi-Da Sun; Yun-Jian Zhang; Lie-Gang Liu (Neuroscience Bulletin, 2009)

Preparation and In Vitro Evaluation of Solid Dispersions of Total Flavones of Hippophae rhamnoides L. - Yan Xie; Guowen Li; Xiurong Yuan; Zhenzhen Cai; Rong Rong (AAPS PharmSciTech, 2009)

Gene mapping related to yellow green leaf in a mutant line in rice (Oryza sativa L.) - Peng Du; Ying-Hua Ling; Xian-Chun Sang; Fang-Ming Zhao; Rong Xie; Zheng-Lin Yang; Guang-Hua He (Genes & Genomics, 2009)

Expression analysis and genetic mapping of three SEPALLATA-like genes from peach (Prunus persica (L.) Batsch) - Yong Xu; Lin Zhang; Hua Xie; Yan-Qiu Zhang; M. Margarida Oliveira; Rong-Cai Ma (Tree Genetics & Genomes, 2008)

Application of NIR spectroscopy for firmness evaluation of peaches - Xia-ping FU; Yi-bin Ying; Ying Zhou; Li-juan Xie; Hui-rong Xu (Journal of Zhejiang University-SCIENCE B, 2008)

Expression, purification and characterization of a phyA m -phyCs fusion phytase - Li-kou Zou; Hong-ning Wang; Xin Pan; Guo-bao Tian; Zi-wen Xie; Qi Wu; Hui Chen; Tao Xie; Zhi-rong Yang (Journal of Zhejiang University-SCIENCE B, 2008)

Polymorphisms in intron 1 of the porcinePOU1F1 gene - Cheng-Yi Song; Bo Gao; Shang-Hui Teng; Xiao-Yang Wang; Fei Xie; Guo-hong Chen; Zhi-Yue Wang; Rong-bin Jing; Jiu-De Mao (Journal of Applied Genetics, 2007)

A Novel Glycosylphosphatidylinositol-Anchored Alkaline Phosphatase Dwells in the Hepatic Duct of the Pearl Oyster, Pinctada fucata - Li-Ping Xie*; Yuan-Tai Wu*; Yi-Ping Dai; Qing Li; Rong-Qing Zhang (Marine Biotechnology, 2007)

Heregulin protects mesenchymal stem cells from serum deprivation and hypoxia-induced apoptosis - Chun Gui; Jian An Wang; Ai Na He; Tie Long Chen; Rong Hua Luo; Jun Jiang; Xin Yang Hu; Xiao Jie Xie (Molecular and Cellular Biochemistry, 2007)

Apelin suppresses apoptosis of human osteoblasts - Hui Xie; Ling-Qing Yuan; Xiang-Hang Luo; Jiao Huang; Rong-Rong Cui; Li-Juan Guo; Hou-De Zhou; Xian-Ping Wu; Er-Yuan Liao (Apoptosis, 2007)

Detection of Survivin-expressing circulating cancer cells in the peripheral blood of breast cancer patients by a RT-PCR ELISA - Shang-Mian Yie; Bie Luo; Nai-Yao Ye; Ke Xie; Shang-Rong Ye (Clinical & Experimental Metastasis, 2006)

Bone marrow mesenchymal stem cell transplantation combined with perindopril treatment attenuates infarction remodelling in a rat model of acute myocardial infarction - Jian-an Wang; Rong-hua Luo; Xing Zhang; Xiao-jie Xie; Xin-yang Hu; Ai-na He; Jie Chen; Jia-hui Li (Journal of Zhejiang University-SCIENCE B, 2006)

SSR allelic variation in almond (Prunus dulcis Mill.) - Hua Xie; Yi Sui; Feng-Qi Chang; Yong Xu; Rong-Cai Ma (Theoretical and Applied Genetics, 2006)

Characterization of a human Sec14-like protein cDNA SEC14L3 highly homologous to human SPF/TAP - Xin Ye; Chaoneng Ji; Gang Yin; Rong Tang; Li Zeng; Shaohua Gu; Kang Ying; Yi Xie; Robert Chunhua Zhao; Yumin Mao (Molecular Biology Reports, 2004)

The Immunoregulation of Mice by Somatic Transgenic Expression of Porcine Interleukin-6 Gene and CpG Sequence - Jiangling Li; Rong Gao; Mei Wu; Mingjie Meng; Manshu Tang; Yi Shen; Lihuan Wang; Xueyan Wu; Xue Yin; Hongguan Xie; Shigui Liu (Veterinary Research Communications, 2004)

Isolation and characterization of a human putative receptor protein kinase cDNA STYK1* - Xin Ye; Chaoneng Ji; Qingshan Huang; Chao Cheng; Rong Tang; Jian Xu; Li Zeng; Jianfeng Dai; Qihan Wu; Shaohua Gu; Yi Xie; Yumin Mao (Molecular Biology Reports, 2003)

Cloning, expression and genomic structure of a novel human GNB2L1 gene, which encodes a receptor of activated protein kinase C (RACK)* - Shu Wang; Jin-zhong Chen; Zhen Zhang; Shaohua Gu; Chaoneng Ji; Rong Tang; Kang Ying; Yi Xie; Yumin Mao (Molecular Biology Reports, 2003)

Cloning and identification of a cDNA that encodes a novel human protein with thrombospondin type I repeat domain, hPWTSR - Jin-Zhong Chen; Shu Wang; Rong Tang; Quan-Sheng Yang; Enpeng Zhao; Yaoqiong Chao; Kang Ying; Yi Xie; Yu-Min Mao (Molecular Biology Reports, 2002)

A novel human hydroxysteroid dehydrogenase like 1 gene (HSDL1) is highly expressed in reproductive tissuesa - Yan Huang; Rong Tang; Jianfeng Dai; Shaohua Gu; Wei Zhao; Chao Cheng; Ming Xu; Zongxiang Zhou; Kang Ying; Yi Xie; Yumin Mao (Molecular Biology Reports, 2001)

Cloning and Characterization of KLHL5, a Novel Human Gene Encoding a Kelch-Related Protein with a BTB Domain - Shu Wang; Zongxiang Zhou; Kang Ying; Rong Tang; Yan Huang; Chaoqun Wu; Yi Xie; Yumin Mao (Biochemical Genetics, 2001)

Identification of a Human LNX Protein Containing Multiple PDZ Domains - Yi Xie; Wei Zhao; Wei Wang; Sihui Zhao; Rong Tang; Kang Ying; Zongxiang Zhou; Yumin Mao (Biochemical Genetics, 2001)

Ribozyme-mediated resistance to rice dwarf virus and the transgene silencing in the progeny of transgenic rice plants - Shengcheng Han; Zujian Wu; Huaiyi Yang; Rong Wang; Yin Yie; Lianhui Xie; Po Tien (Transgenic Research, 2000)